Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 31258516 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Canthigaster valentini (Bleeker, 1853), Gymnothorax buroensis (Bleeker, 1857), Parupeneus barberinus (Lacepède, 1801), Uropterygius supraforatus (Regan, 1909), Chaetodon vagabundus Linnaeus, 1758, Mysis relicta Lovén, 1862, Cyprinus carpio Linnaeus, 1758, Perca flavescens (Mitchill, 1814), Bracca maculosa Walker, 1856, Gymnoscelis fasciata Hampson, 1895, Ozola falcipennis Moore, 1888, Tasta montana, Chamaesaracha sordida (Dunal) A.Gray, Houstonia humifusa (Engelm. ex A.Gray) A.Gray, Physalis hederifolia A.Gray, Allium ursinum L., Cerastium fontanum Baumg., Euphorbia amygdaloides L., Linaria repens (L.) Mill., Prunus avium (L.) L., Veronica officinalis L., Austrolimnophila ochracea (Meigen, 1804), Dixa dilatata Strobl, 1900, Halesus digitatus (von Paula Schrank, 1781), Hydroporus umbrosus (Gyllenhal, 1808), Nebrioporus depressus (Fabricius, 1775), Potamophylax cingulatus (Stephens, 1837), Simulium reptans Linnaeus, 1758, Anacaena limbata (Fabricius, 1792), Hydraena palustris Erichson, 1837, Pedicia rivosa (Linnaeus, 1758), Berula erecta (Huds.) Coville, Lemna gibba L., Nasturtium officinale R.Br., Littorella uniflora (L.) Asch., Alnus glutinosa (L.) Gaertn., Brassica rapa L., Centaurea nigra L., Dicranum majus Turner, 1804, Festuca vivipara (L.) Sm., Hypericum androsaemum L., Linaria vulgaris Mill., Oreopteris limbosperma (All.) Holub, Pleurozium schreberi Mitten, 1869, Rorippa palustris (L.) Besser, Selaginella selaginoides (L.) Schrank & C.F.P.Mart., Thalictrum alpinum L., Veronica scutellata L., Blackstonia perfoliata (L.) Huds., Clinopodium vulgare L., Heracleum mantegazzianum Sommier & Levier, Meconopsis cambrica Linnaeus, 1753, Polygala calcarea F.W.Schultz, Sinapis alba L., Vinca minor L., Cathartes aura (Linnaeus, 1758), Numenius phaeopus (Linnaeus, 1758), Abludomelita obtusata (Montagu, 1813), Campylaspis costata (Sars, 1865), Euclymene droebachiensis (Sars, 1872), Leucothoe lilljeborgi Boeck, 1861, Oxydromus flexuosus (Delle Chiaje, 1827), Samytha sexcirrata (M.Sars, 1856), Tmetonyx cicada (Fabricius, 1780), Emberiza cirlus Linnaeus, 1766, Phylloscopus trochilus (Linnaeus, 1758), Iridomyrmex suchieri, Allium canadense L., Bromus inermis Leyss., Eleocharis elliptica Kunth, Houstonia caerulea L., Lycopus americanus Muhl. ex W.P.C.Barton, Polygala polygama Walter, Scirpus acutus Muhl., 1817, Thalictrum dasycarpum Fisch., Mey. & Avé-Lall., Campanula rapunculus L., Hieracium murorum L., Ranunculus lanuginosus L., Potamogeton compressus L., Poecilia sphenops Valenciennes, 1846, Micropterus punctulatus (Rafinesque, 1819), Lithobates sylvaticus (LeConte, 1825), Poa alpina L., Campsis radicans (L.) Seem., Chelone glabra L., Hordeum jubatum L., Phyla lanceolata (Michx.) Greene, Sparganium eurycarpum Engelm., Otis tarda Linnaeus, 1758, Ralfsia fungiformis Nagai, 1940, Bromus rigidus Roth, Marcus-Kochia ramosissima (Desf.) Al-Shehbaz, Sporobolus versicolor (Fabre) P.M.Peterson & Saarela, Lamium maculatum (L.) L., Anthidium cockerelli Schwarz, 1928, Colletes intermixtus Swenk, 1905, Lasioglossum diversopunctatum (Ellis, 1914), Melissodes perpolitus LaBerge, 1961, Perdita verbesinae Cockerell, 1896, Dieunomia triangulifera (Vachal, 1897), Xenoglossa strenua (Cresson, 1879), Pelecanoides georgicus Murphy & Harper, 1916, Astarte borealis (Schumacher, 1817), Facelina bostoniensis (Couthouy, 1838), Actinia equina (Linnaeus, 1758), Neoamphitrite figulus (Dalyell, 1853), Ulva rigida C.Agardh, Ulva flexuosa Wulfen, Poecilochaetus serpens Allen, 1904, Aora gracilis (Spence Bate, 1857), Ebalia cranchii Leach, 1817, Gari costulata (W.Turton, 1822), Thalassiosira decipiens (Grunow) E.G.Jørgensen, 1905, Dinobryon balticum (Schütt) Lemmerm., Licmophora ehrenbergii (Kützing) Grunow, 1867, Isias clavipes Boeck, 1865, Semisuberites cribrosa (Miklucho-Maclay, 1870), Securiflustra securifrons (Pallas, 1766), Parasagitta elegans (Verrill, 1873), Gaetanus brevispinus (Sars G.O., 1900), Thysanoessa longicaudata (Krøyer, 1846), Carangoides equula (Temminck & Schlegel, 1844), Chaetodermis penicilligerus (Cuvier, 1816), Carangoides coeruleopinnatus (Rüppell, 1830), Zeus faber Linnaeus, 1758, Diodon holocanthus Linnaeus, 1758, Plectorhinchus polytaenia (Bleeker, 1853), Cyclichthys spilostylus (Leis & Randall, 1982), Parascombrops philippinensis (Günther, 1880), Platycephalus endrachtensis Quoy & Gaimard, 1825, Rhina ancylostoma Bloch & Schneider, 1801, Epinephelus bleekeri (Vaillant, 1878), Champsodon guentheri Regan, 1908, Nemipterus isacanthus (Bleeker, 1873), Acanthurus dussumieri Valenciennes, 1835, Procellaria cinerea Gmelin, 1789, Variospora thallincola (Wedd.) Arup, Frödén & Søchting, Brongniartella byssoides (Goodenough & Woodward) F.Schmitz, Tubulanus annulatus (Montagu, 1804), Taonia atomaria (Woodw.) J.Agardh, Mycale macilenta (Bowerbank, 1866), Botrylloides leachii (Savigny, 1816), Emarginula fissura (Linnaeus, 1758), Phisidia aurea Southward, 1956, Parapleustes bicuspis (Krøyer, 1838), Ptilota gunneri P.C.Silva, Maggs & L.M.Irvine, Corella parallelogramma (Müller, 1776), Echinogammarus marinus (Leach, 1815), Anomia ephippium Linnaeus, 1758, Rhodothamniella floridula (Dillwyn) Feldmann, Vitreolina philippi (de Rayneval & Ponzi, 1854), Coryne pusilla Gaertner, 1774, Gadus morhua Linnaeus, 1758, Synmerosyllis lamelligera (Saint-Joseph, 1887), Lesueurigobius friesii (Malm, 1874), Smittoidea reticulata (MacGillivray, 1842), Nothria conchylega (Sars, 1835), Idotea pelagica Leach, 1816, Perophora listeri Wiegman, 1835, Scruparia chelata (Linnaeus, 1758), Lytocarpia myriophyllum (Linnaeus, 1758), Cyrillia linearis (Montagu, 1803), Eatonina fulgida (J.Adams, 1797), Bugulina stolonifera (Ryland, 1960), Microphthalmus listensis Westheide, 1967, Ceramium strictum Kutzing, Longipedia minor Scott T. & Scott A., 1893, Laophonte elongata Boeck, 1873, Chirona hameri (Ascanius, 1767), Cladophora battersii Hoek, 1963, Coryphaena hippurus Linnaeus, 1758, Hippopodius hippopus (Forsskål, 1776), Enneagonum hyalinum Quoy & Gaimard, 1827, Trachyrincus scabrus (Rafinesque, 1810), Benthalbella infans Zugmayer, 1911, Eustomias simplex Regan & Trewavas, 1930, Rajella bigelowi (Stehmann, 1978), Cuvierina columnella (Rang, 1827), Diaphus subtilis Nafpaktitis, 1968, Ichthyococcus ovatus (Cocco, 1838), Rhopalonema funerarium Vanhöffen, 1902, Scina borealis (G.O.Sars, 1883), Proceroecia procera (G.W.Müller, 1894), Bathypterois dubius Vaillant, 1888, Taaningichthys paurolychnus Davy, 1972, Astyra bogorovi Birstein & M.Vinogradov, 1955, Scina similis Stebbing, 1895, Gaidropsarus argentatus (Reinhardt, 1837), Echinaster farquhari Benham, 1909, Phycis chesteri Goode & Bean, 1878, Menidia menidia (Linnaeus, 1766), Cetorhinus maximus (Gunnerus, 1765), Coris flavovittata (Bennett, 1828), Caudina arenata (Gould, 1841), Hyporthodus niveatus (Valenciennes, 1828), Prognathodes aya (Jordan, 1886), Stephanollona longispinata (Busk, 1884), Calyptotheca immersa (Powell, 1967), Watersipora subtorquata (d'Orbigny, 1852), Alderina pacifera (Gordon, 1986), Crisia setosa MacGillivray, 1869, Cellaria pilosa (Kirchenpauer, 1869), Celleporaria tridenticulata (Busk, 1881), Hiantopora jucunda Gordon, 1984, Nolella stipata Gosse, 1855, Macruronus novaezelandiae (Hector, 1871), Coryphaenoides dossenus McMillan, 1999, Sphyrna zygaena (Linnaeus, 1758), Dermechinus horridus (A.Agassiz, 1879), Melanonus zugmayeri Norman, 1930, Enteroctopus zealandicus (Benham, 1944), Nesiarchus nasutus Johnson, 1862, Brama australis Valenciennes, 1838, Melita nitida S.I.Smith, 1873, Ameritella agilis (Stimpson, 1857), Cyclaspis varians Calman, 1912, Kurtiella planulata (Stimpson, 1851), Microphiopholis atra (Stimpson, 1852), Campylaspis affinis Sars, 1870, Pseudohaustorius caroliniensis Bousfield, 1965, Gammarus daiberi Bousfield, 1969, Aricidea alisdairi Hasan, 1960, Cylichna gouldii (Couthouy, 1839), Boccardiella ligerica (Ferronnière, 1898), Uromunna hayesi (Robertson, 1978), Prionospio dayi (Foster, 1969), Lysidice ninetta Audouin & H Milne Edwards, 1833, Hermundura fauveli (Berkeley & Berkeley, 1941), Scoloplos capensis (Day, 1961), Abra lioica (Dall, 1881), Magelona cincta Ehlers, 1908, Pinnixa lunzi Glassell, 1937, Gouldia cerina (C.B.Adams, 1845), Tampaella mera (Say, 1838), Erichsonella crenulata Menzies, 1950, Eusarsiella childi Kornicker, 1986, Mexieulepis mexicanus (Berkeley & Berkeley, 1939), Semele bellastriata (Conrad, 1837), Paraprionospio treadwelli (Hartman, 1951), Donax texasianus Philippi, 1847, Semele purpurascens (Gmelin, 1791), Acanthochitona hemphilli (Pilsbry, 1893), Sebastes polyspinis (Taranetz & Moiseev, 1933), Eumicrotremus orbis (Günther, 1861), Sebastes pinniger (Gill, 1864), Bathyraja maculata Ishiyama & Ishihara, 1977, Icelus spiniger Gilbert, 1896, Hemilepidotus papilio (Bean, 1880), Chen caerulescens (Linnaeus, 1758), Eulithis xylina Hulst, 1896, Provanna glabra Okutani, Tsuchida & Fujikura, 1992, Natsushima bifurcata Miura & Laubier, 1990, Nicomache ohtai Miura & Hashimoto, 1991, Lucicutia flavicornis (Claus, 1863), Rossia pacifica Berry, 1911, Liparis pulchellus Ayres, 1855, Lycodapus fierasfer Gilbert, 1890, Spirontocaris ochotensis (J.F.Brandton Middendorf, 1851), Ogcocephalus vespertilio (Linnaeus, 1758), Ogcocephalus parvus Longley & Hildebrand, 1940, Acanthurus coeruleus Bloch & Schneider, 1801, Nereis panamensis Fauchald, 1977, Nuuanu muelleri Ortiz, 1976, Eusarsiella greyi (Darby, 1965), Raninoides laevis (Latreille, 1825), Nannodiella oxia (Bush, 1885), Eudorella pacifica Hart, 1930, Photis californica Stout, 1913, Aricidea ramosa Annenkova, 1934, Eunice impexa Grube, 1878, Barbatia candida (Helbling, 1779), Pleurobranchaea californica MacFarland, 1966, Lirularia lirulata (Carpenter, 1864), Melphisana bola J.L.Barnard, 1962, Parvamussium cancellatum (E.A.Smith, 1885), Spathochlamys benedicti (A.E.Verrill & Bush, 1897), Atlantilux gemmata (G.B.Sowerby II, 1874), Megasyllis nipponica (Imajima, 1966), Artacama coniferi Moore, 1905, Macoma carlottensis Whiteaves, 1880, Bruzelia tuberculata G.O.Sars, 1883, Serranus baldwini (Evermann & Marsh, 1899), Chromis multilineata (Guichenot, 1853), Lutjanus mahogoni (Cuvier, 1828), Bollmannia boqueronensis Evermann & Marsh, 1899, Pagurus acadianus Benedict, 1901, Nuculana tenuisulcata (Couthouy, 1838), Campylaspis horrida Sars, 1870, Aegiochus ventrosa (M.Sars, 1859), Meterythrops robusta S.I.Smith, 1879, Kinetoskias smitti Danielssen, 1868, Xylonora atlantica (H.G.Richards, 1942), Turbonilla elegantula A.E.Verrill, 1882, Mendicula pygmaea (Verrill & Bush, 1898), Coccyzus americanus (Linnaeus, 1758), Aphelocoma coerulescens (Bosc, 1795), Thryomanes bewickii (Audubon, 1827), Troglodytes aedon Vieillot, 1809, Pheucticus ludovicianus (Linnaeus, 1766), Sphyrapicus ruber (J.F.Gmelin, 1788), Selasphorus rufus (J.F.Gmelin, 1788), Sphyrapicus thyroideus (Cassin, 1852), Petrochelidon fulva (Vieillot, 1808), Dentalium agassizi Pilsbry & Sharp, 1897, Thracia morrisoni Petit, 1964, Eclysippe eliasoni (Day, 1973), Pseudoscalibregma parvum (Hansen, 1879), Polyipnus clarus Harold, 1994, Archosargus probatocephalus (Walbaum, 1792), Bregmaceros atlanticus Goode & Bean, 1886, Histioteuthis corona (Voss & Voss, 1962), Coryphaena equiselis Linnaeus, 1758, Tsuga mertensiana (Bong.) Carrière, Notropis spectrunculus (Cope, 1868), Krefftichthys anderssoni (Lönnberg, 1905), Pogonophryne permitini Andriashev, 1967, Polyarthra euryptera Wierzejski, 1891, Daphnia ambigua Scourfield, 1947, Leiocottus hirundo Girard, 1856, Pisaster giganteus (Stimpson, 1857), Prionitis lanceolata, Hygophum hanseni (Tåning, 1932), Antipodocottus elegans Fricke & Brunken, 1984, Acanthaster planci (Linnaeus, 1758), Ficinia paradoxa (Schrad.) Nees, Erica gnaphaloides Thunb., Erica plukenetii L., Agathosma hookeri Sond., Pharnaceum lanuginosum J.C.Manning & Goldblatt, Chironia linoides L., Capeobolus brevicaulis (C.B.Clarke) Browning, Geranium incanum Burm.f., Cineraria geifolia (L.) L., Restio saroclados Mast., Noctiluca scintillans (Macartney) Kof. & Swezy, Labidocera minuta Giesbrecht, 1889, Oithona simplex Farran, 1913, Lucifer typus H.Milne Edwards, 1837, Corycaeus vitreus Dana, 1849, Tripos contortus (Gourret) F.Gómez, Chaetoceros septentrionalis Cleve, 1896, Bacteriastrum comosum Pavillard, Buckinghamia celsissima F.Muell., Rhodamnia costata A.J.Scott, Myristica insipida R.Br., Sloanea macbrydei F.Muell., Alstonia muelleriana Domin, Cnesmocarpon dasyantha (Radlk.) Adema, Oraniopsis appendiculata (F.M.Bailey) J.Dransf., A.K.Irvine & N.W.Uhl, Normanbya normanbyi (W.Hill) L.H.Bailey, Dysoxylum alliaceum (Blume) Blume, Syzygium monospermum Craven, Limicola falcinellus (Pontoppidan, 1763), Mesechthistatus binodosus (Waterhouse, 1881), Domene curtipennis Sharp, 1889, Carabus insulicola Chaudoir, 1869, Chromis lineata Fowler & Bean, 1928, Chaetodon flavirostris Günther, 1874, Cheiloprion labiatus (Day, 1877), Galaxias postvectis Clarke, 1899, Ciliata septentrionalis (Collett, 1875), Boops boops (Linnaeus, 1758), Megastraea undosa (W.Wood, 1828), Spicara smaris (Linnaeus, 1758), Dardanus arrosor (Herbst, 1796), Dasyatis pastinaca (Linnaeus, 1758), Carollia brevicaudum (Schinz, 1821), Dipodomys spectabilis Merriam, 1890, Scorpaena scrofa Linnaeus, 1758, Aythya marila (Linnaeus, 1761), Cupido minimus (Fuessly, 1775), Barringtonia racemosa (L.) Spreng., Oligosarcus pintoi Amaral Campos, 1945, Pseudorasbora parva (Temminck & Schlegel, 1846), Pseudomugil signifer Kner, 1866, Cottus poecilopus Heckel, 1837, Noturus gyrinus (Mitchill, 1817), Lates niloticus (Linnaeus, 1758), Cyprinella whipplei Girard, 1856, Macquaria australasica Cuvier, 1830, Cottus caeruleomentum Kinziger, Raesly & Neely, 2000, Cyprinella callistia (Jordan, 1877), Etheostoma thalassinum (Jordan & Brayton, 1878), Pachychilon pictum (Heckel & Kner, 1858), Aulacorthum solani (Kaltenbach, 1843), Nebria salina Fairmaire & Laboulbène, 1854, Harpalus solitaris Dejean, 1829, Pterostichus minor (Gyllenhal, 1827), Noctua janthina Denis & Schiffermüller, 1775, Hoplodrina octogenaria (Goeze, 1781), Cosmorhoe ocellata (Linnaeus, 1758), Idaea rusticata (Denis & Schiffermüller, 1775), Athetis furvula (Hübner, 1808), Achlya flavicornis (Linnaeus, 1758), Cleora cinctaria (Denis & Schiffermüller, 1775), Euxoa aquilina (Denis & Schiffermüller, 1775), Sphinx ligustri Linnaeus, 1758, Plagodis pulveraria (Linnaeus, 1758), Heliothis viriplaca (Hufnagel, 1766), Noctua interposita (Hübner, 1790), Hyalostenele oleagina Warren, 1894, Aplocera praeformata (Hübner, 1826), Sideridis turbida (Esper, 1790), Orthosia populeti (Fabricius, 1775), Lemonia dumi (Linnaeus, 1761), Crocallis tusciaria (Borkhausen, 1793), Caradrina aspersa Rambur, 1834, Carabus germarii Sturm, 1815, Archichauliodes diversus (Walker, 1853), Aelia acuminata (Linnaeus, 1758), Adelphocoris lineolatus (Goeze, 1778), Dictyla humuli (Fabricius, 1794), Coreus marginatus (Linnaeus, 1758), Athysanus quadrum Boheman, 1845, Anaceratagallia frisia (Wagner, 1939), Nigrobaetis digitatus (Bengtsson, 1912), Aquarius paludum (Fabricius, 1794), Glaenocorisa propinqua (Fieber, 1861), Caenis pusilla Navás, 1913, Ceraclea albimacula (Rambur, 1842), Chelicorophium curvispinum (G.O.Sars, 1895), Hygrotus impressopunctatus (Schaller, 1783), Euproctis pulverea Hampson, 1900, Scopula pudicaria Motschulsky, 1866, Kentrochrysalis streckeri, Auaxa sulphurea, Comostola subtiliaria Bremer, 1864, Jodis dentifascia Warren, 1897, Sineugraphe stolidoprocta Boursin, 1954, Scopula impersonata, Hypena sagitta (Fabricius, 1775), Xanthorhoe hortensiaria Graeser, 1889, Eupithecia interpunctaria Inoue, 1979, Tethea consimilis Warren, 1912, Heliophobus dissectus Walker, 1865, Chloroclystis consueta Butler, 1879, Spodoptera depravata Butler, 1879, Calyptra hokkaida Wileman, 1922, Aedes grossbecki Dyar & Knab, 1906, Bembidion mannerheimii C.R.Sahlberg, 1827, Eupithecia centaureata (Denis & Schiffermüller, 1775), Eulithis testata (Linnaeus, 1761), Eupithecia lariciata (Freyer, 1841))", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 31258516 records from 5733 constituent datasets: 8 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 40 records from 2019_KNUN_fish. 94 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 13 records from Herbarium of University of Białystok - Vascular Plants. 46 records from Fig 14. Pollen profile from sediment core Schmiecher See. 4 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 3 records from Données de la structure ACOREP provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from mabik_fl. 12 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 9 records from SSNATV_2017_12_18. 8202 records from CRBPO : STOC, Baguage. 122 records from Naturalis Biodiversity Center (NL) - Cnidaria. 7 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 44 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE241. 2 records from Inventaire du site Pierre Fabre de Cahors. 1 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 47 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 7 records from Aves de la expedición en la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 30 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 2 records from Vorderer Tiergarten (Dessau). 2 records from Données naturalistes d'Olivier LAURENT. 1 records from Kindergarten. 143 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 788 records from Canadian Museum of Nature Herbarium. 73 records from Données naturalistes de RAYNARD Philippe. 17 records from 1966-1986 T.G. Skinner Solway Firth Occurrence of some prominent zooplankton. 92 records from Lepidoptera (Specimens NRM). 10 records from Colección Mastozoológica-Museo de Historia Natural Unillanos. 3 records from Banco de Germoplasma del Real Jardín Botánico Juan Carlos I. 4 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 30 records from Mosses and Liverworts: Records for Kent.. 12 records from Birds (GMBO-BI). 34 records from Biodiversidad asociada al gasoducto Paiva-Caracolí. 28 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 2 records from Colección de macroalgas de la costa Argentina (INIBIBB-UNS-CONICET). 14 records from Invasive Plant Atlas of the MidSouth (IPAMS). 5 records from Inventaire "Espaces Naturels Sensibles" du Plata (SORE). 21 records from Biodiversity of the Desna river valley and its tributaries. 5 records from Bannwald Burghauser Forst. 1 records from Données naturalistes de EL ATTAR SOFI OUMAYMA. 11 records from Pollen analysis of sediment profile MU1 from Muggesfelder See. 15 records from Códigos de barras de la vida en peces y zooplancton de México. 142 records from Community Foundation for Ireland Records. 2871 records from SYKO Herbarium Moss Collection. 22 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 160 records from Marie-Victorin Herbarium (MT) - Bryophytes. 4447 records from Florida Keys Reef Visual Census 1999. 5 records from iHerbarium. 8 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 5 records from 2019_biodiversity_cooperation_investigation. 258 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 4 records from Données du/de la naturaliste Chiron François provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Plant specimens of Tama City Cultural Foundation. 2 records from flower availability 2008 Alb-korrigiert. 156 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 2 records from Données multi sources collectées par Hanot Christophe, pour l'atlas des Cerambycidae de métropole (lot 2017). 46 records from Freshwater fishes of Greece. 34 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 42 records from TransForest - vegetation, lichen and fungi data 2016. 201 records from Biowide Species data. 6 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 17 records from Macrobenthos Chukchi Sea, 1986. 21 records from Catalogue Lhomme 1923-[1963]. 4 records from Schanzenanlage Bergham. 4 records from Herbarium of the Institute of the problems of Northern development (TMN). 10 records from St Andrews BioBlitz 2015. 3 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 1 records from Comparative study in validity of three regions of 18S-rRNA for eukaryote amplicon sequence analyses. 13185 records from Observational database of Icelandic plants. 1 records from Dörnberg. 179 records from sarce_rockyshores. 36 records from AMAPPS Northeast Aerial Cruise Summer 2010. 2 records from Données espèces - Expertise IPE 9. 23 records from Murciélagos observados en la expedición al Río Apaporis - Proyecto Colombia BIO. 2833 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 29 records from Brown University. 41 records from ZMMU MSU, White Sea Branch. 1 records from Southern Highlands Nature Map. 35 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 7 records from Flora genérica de las gramíneas del estado de Tlaxcala. 199 records from MZFC/Coleccion de Aves. 1 records from Manx Wildlife Trust - Records. 7 records from Bulau. 35 records from Données naturalistes de Ségolène FAUSTEN. 3 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 74 records from Natural History Museum Maastricht (NL) - Herbarium. 1 records from 2010-2013 Beetle Data from Machair LIFE+ Project Plots. 57 records from Spatial and temporal ichthyofauna community of a tropical mangrove Bay (Gazi Bay, Kenya) sampled between 1994 and 1996. 1035823 records from Artportalen (Swedish Species Observation System). 22 records from DMNS Egg Collection (Arctos). 1 records from Tejidos colectados en la expedición al municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 85 records from Lepidopterous specimens of Yamagata Prefectural Museum. 3 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 53 records from Helgeland Museum, Lepidoptera. 45 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Ictiología. 1 records from Plant (KIWE-PL). 173 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 2 records from Murciélagos de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 61 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 31 records from List of the specimens of the Vanuatu National Herbarium (PVNH). 8331 records from Florida Keys Reef Visual Census 2014. 111 records from Seabird temporal composition, abundance and habitat use in “Punta La Metalera” (Arequipa), Southern Peru. 2 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 4 records from Colección de Poales del Museo Botánico CORD - IMBIV. 79 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Zooplancton Chetumal). 122 records from Overvåking av åpen grunnlendt kalkmark i Oslofjordområdet. 10 records from Benthos Chirnov Basin 1986 and 2002. 575 records from Inventaire de la flore de Lot-et-Garonne 2018. 758 records from Queensland Museum provider for OZCAM. 51 records from Bryophyte Herbarium (H): Herbarium Fennoscandiae orientalis. 751 records from Herbarium Universitatis Daugavpiliensis. 81 records from Bruce Bennett Herbarium (BABY). 3 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 2 records from Spießwoogtal / Königsbruch (Fischbach). 39 records from IPAE egg clutches collection (Aves). 5 records from Données espèces - Expertise IPE 93. 4 records from Abundance and habitat of echinoderms collected during the Bangor-Watamu Expedition in 1969. 8 records from Vascular Plants from Praia da Vitória (Terceira, Azores, Portugal). 54 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 2 records from Inventario de Fauna Vertebrada de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. 70 records from Danish Plant Bugs (Miridae). 52 records from KTU Pteridophyta. 2 records from Ortelsbruch - Hangmoor bei Morbach. 78 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 21 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 1998. 2 records from Sherwood Arboretum Botanical Collection Dataset. 1213 records from Données naturalistes d'Olivier ESCUDER. 22 records from Données d'expertise convention GTM Bâtiment et le Service du patrimoine naturel du MNHN. 4 records from Aves of wetlands and protected forests in Benin. 1 records from Sonidos de aves, anfibios, mamíferos e insectos del departamento de Santander - Proyecto Santander BIO. 9 records from Artenvielfalt der Nordsee - Helgoland. 9 records from ANTARCTIC PLANT DATABASE. 41 records from HBRG Invasive Non-native Plants Dataset. 80 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ornithology National Collection (MACNOr). 10 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 11 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 340 records from Inventaire de la flore de Gironde 2018. 2834 records from WildNet - Queensland Wildlife Data. 2 records from Pollen profile V and Ausfluss at Krumbach, Germany. 1 records from BIRDRACE The early birds. 2 records from BIRDRACE Emslandracer. 1 records from Zielbach (Töll). 5 records from SEWBReC Worms (South East Wales). 218 records from Inventaire de la flore du PNRLG 2017 (Landes). 2266 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 2 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 7 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 8 records from Aves asociadas a las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 3455 records from National Plant Monitoring Scheme - England, Scotland, Wales. 12 records from Alien Flora of Nepal at KATH. 45 records from Banco de datos florísticos del Herbario CHAP. 372 records from Birds Specimens. 94 records from University of Michigan Museum of Zoology, Division of Mammals. 5 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 37 records from Effects of elevation gradient and aspect on butterfly diversity on Galičica Mountain in the Republic of Macedonia (south-eastern Europe). 3 records from 2020_biodiversity_information_specimen. 7 records from Upper Silesian Museum, Bird Observations. 197 records from Bird collection NTNU University Museum. 6 records from DMNS Mammal Collection (Arctos). 24 records from Données du/de la naturaliste Vindras Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 62 records from UK Biodiversity Action Plan Invertebrate Data for Wales. 1 records from BIRDRACE NABUhu Trier!. 32 records from Inventaire de la flore de la Vienne 2015. 91 records from mabik_pr. 3 records from InsectScale2008FlowerCover. 57 records from IBF Monitoring of Fungi. 12 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 605 records from The Himalayan Uplands Plant database (HUP Version 1). 1776 records from Inventaire de la flore de Dordogne 2015. 7 records from Herbario Pontificia Universidad Javeriana. 1 records from Mauernacker (Wettsaasen). 298 records from University of Nebraska State Museum Birds Collection. 1 records from FFH-Gebiet Klosterwasser/Burkau. 1 records from University of California Santa Barbara Invertebrate Zoology Collection. 2 records from Wiesen in der Grünen Mitte. 2 records from Avifauna del sector Cabaña Naranjal y Limón Cocha en el Área Protegida La Paya observada durante el Global Big Day de mayo del 2019. 5 records from Censo de aves en el bosque restauración del Parque Nacional Natural Farallones de Cali en el 2012. 19 records from Fish occurrence in Kama River basin. 2 records from Données naturalistes de Hervé BOUYON. 1 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 68 records from Naturhistorisches Museum Mainz, Schmetterlingssammlung Rodenkirchen. 4 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités (Réunion). 2 records from Wildkräuter. 25 records from Données naturalistes de BALLUCK Cindy. 1 records from Entomology Collection at the Natural History Museum of Utah. 5 records from Berlin-Brandenburg Plant Collection 2004. 1 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 13 records from Données DREAL Centre-Val de Loire - Faune - 2018. 432 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 592 records from Australian National Insect Collection. 8 records from ALCB - Herbário Alexandre Leal Costa. 15 records from Registros biológicos de predios promocionados como Reservas Naturales de la Sociedad Civil-RNSC en el Cañón de Amaime, municipio El Cerrito, Valle del Cauca, Colombia.. 1 records from BIRDRACE LiLaLau. 1 records from University of California, Davis, Center for Plant Diversity - Bryophyte Herbarium. 94 records from Fauna presente en el proyecto Minera de Cobre Quebradona, municipio de Jericó. 990 records from Fish specimens of Kagoshima University Museum. 1 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 4 records from Registros biológicos de aves Distrito de Manejo Integrado Musichi y Santuario de Fauna y Flora los Flamencos, La Guajira.. 164 records from Species of plants, fungi and animals from separate territories of Podesinnia. 10 records from Freiburger GEO-Tag der Artenvielfalt. 6520 records from Lithuanian Lepidoptera and Odonata. 40 records from Fish occurrence in Kuban River basin. 22 records from Copepodos Chile. 225 records from Highland bird data 2002 - 2003 - non-breeding records. 49 records from Harriet Irving Botanical Gardens (HIBG). 1 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 101 records from A dataset of bird inventory records at Cloudbridge Nature Reserve, Talamanca Mountains, Costa Rica, between March 2016 and May 2020.. 2 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 89 records from CNIN/Abejas de México/Apoidea. 54 records from bioman_belgium. 174 records from RECORD Freshwater Fish Data. 162 records from Freshwater fish records via iRecord. 19 records from Amplicon sequencing of Tara Oceans RNA samples corresponding to size fractions for protists.. 13 records from Palynology of profile Füramoos III. 91 records from Vascular plants of Amrum 2007-2008. 17 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1 records from NEON Biorepository Mosquito Collection (Pinned Vouchers). 260 records from Colección de Mamíferos del Museo de Historia Natural de la Universidad de la Amazonia (UAM-M). 5 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 44 records from IOW Natural History & Archaeological Society Marine Records. 1 records from Données naturalistes de TEISSEDRE BERTRAND. 91 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 14 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 3 records from Waldi-Weiher. 1 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 6632 records from Phase 2 Lowland Grassland Survey of Wales. 112 records from hymenoptera. 6 records from Gewann Krampf (Heilbronn). 1 records from Naturalis Biodiversity Center (NL) - Crustacea. 2 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 1 records from Kongsfjorden/Spitsbergen - soft bottom fauna. 1 records from Birdrace-Buteo1_DO-Dortmund. 89 records from Algae Herbarium (KMN) UiA. 1 records from SCAR Biogeographic Atlas of the Southern Ocean - Porifera - Data. 6654 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 3013 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 11559 records from DATAVES. 46 records from Flore de l'Ain. 3 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 20434 records from Lajitietokeskus/FinBIF - Notebook, general observations. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 1 records from Schulgarten mit Klasse 8a (Essen). 1 records from Phytoplankton data collected from the Black Sea during April 1952 (Cruise 3). 8 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 1 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 1 records from Birdrace-Bielefinken-Bielefeld. 81 records from Ecosphère_2017_12_18. 94 records from Fish specimens of Toyama Science Museum. 2 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 1 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 5 records from Müritz-Nationalpark. 11 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 374 records from Estonian Museum of Natural History Department of Zoology. 1 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 4203 records from Fermanagh Flora. 1 records from Sonidos de la Ecoreserva Campo Rubiales (Puerto Gaitán, Meta) - Proyecto FIBRAS. 552 records from Royal Belgian Institute of Natural Sciences Bird collection. 648 records from KiEco Freshwater Ecology: River Macroinvertebrates. 187 records from Fish of the Recherche Archipelago , Western Australia (2002). 1936 records from National Benthic Inventory. 4 records from Texas Tech University - Invertebrate Zoology. 66 records from Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 187 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 161957 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 216 records from New Zealand Arthropod Collection (NZAC). 4 records from Mise en place d'un suivi scientifique des odonates pour la production d’indicateurs de biodiversité. 1403 records from Canadian Museum of Nature Bird Collection. 2 records from Birdrace-Team_Wangerooge-Friesland. 12 records from CMC_ornithology_GRC. 1 records from BIRDRACE Die Wendehälse. 1 records from Mauervegetation,Flechten und anderes. 150 records from BCE butterfly data expert holiday data throughout Europe. 34919 records from Point counts of breeding terrestrial birds. 3 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 2 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 597 records from National River Water Quality Network Database (Macro-invertebrates) 1990-2008. 7 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 2 records from Birdrace-Die_Nachtraben-Stuttgart. 5 records from Inventaire biodiversité du site Pierre Fabre de Saint-Sulpice. 4 records from Artenvielfalt des "Grünen Klassenzimmers". 8 records from Fungi and Lichens, Outer Hebrides. 30 records from Mollusca fauna from the Mediterranean reef ecosystem (1170 habitat). 1 records from Museu de Ciències Naturals de Barcelona: BGJBB. 1 records from Portuguese Decapoda Crustacea - Museu Nacional de História Natural e da Ciência collections. 16 records from Données de type contact en Guadeloupe. 37 records from Balsfjord Nature Reserves. 1 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 4354 records from Kastikka Floristic Archives (KEVO). 5130 records from Sustainable Rivers Audit. 1 records from Waldsee. 617 records from Irish Crop Wild Relative Database. 12 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla (Peces). 2 records from Bizzenbachtal (Wehrheim/Taunus). 87 records from Manx Biological Recording Partnership UNVERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 392 records from IRKU Herbarium: collections of vascular plants. 1 records from Mississippi Entomological Museum. 2 records from Inventaire biodiversité du site Pierre Fabre d'Aignan. 1 records from GERECO_Environnement_2017_12_18. 1 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 20 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 25176 records from Belgian IFBL Flora Checklists (1939-1971). 1 records from BIRDRACE accipiter hardcore birding. 156 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 2 records from MCP-Aves - Coleção de Aves. 137 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 15 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 111 records from Collections of Bioclass, school #179, Moscow. 289 records from BLM CETAP AIR Sightings. 114 records from Wild bees of Grand Staircase-Escalante National Monument. 4 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 2 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 5 records from Wald am Schloss Wittgenstein Bad Laasphe. 638 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 87 records from A dataset from bottom trawl survey around Taiwan. 572 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 37 records from Isle of Wight non-native invasive species. 1 records from R - Herbário do Museu Nacional. 51 records from The DNA and Sample Repository at AIT. 10 records from Colección del Banco de Germoplasma de la Universitat de València. 324 records from Données naturalistes de LUPOLI Roland. 2 records from Sea ice and seawater Raw sequence reads. 6 records from Floristic records in the Moscow and Novgorod regions. 74 records from Insect specimens of Komatsu City Museum. 28 records from Weber State University Herbarium. 19 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 4 records from Biodiversidad asociada al proyecto Conexión Urabá - Nueva Colonia - Apartadó a 110 kV, Antioquia. 1 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 16222 records from Données STOC-EPS. 1 records from Schulgarten der Hainbuchenschule (Hagenbach). 1 records from Données naturalistes de François BRETON. 168 records from Lothian Wildlife Information Centre Secret Garden Survey. 4 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 1 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 1 records from Planktonic copepods from coastal and inshore waters of Tudor Creek, Mombasa (December 1984-March 1985). 6 records from Mayfly (Ephemeroptera) records from Britain and Ireland, via iRecord. 3 records from UNCW Aerial Survey 1998-1999. 2 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 349 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 1 records from Birdrace-SportfreundeTriller-Münster. 33 records from Censos de aves en los municipios de Honda (Tolima) y Guaduas (Cundinamarca) - BIO Alas, cantos y colores. 252 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 137 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 51 records from Données faune Nature 18 - 2017. 643 records from Natural History Museum, Vienna - Herbarium W. 1 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 873 records from Quadrige. 10 records from Données naturalistes de Pascal REVAULT. 105 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 9 records from Estimación de la diversidad de Copepoda en el área de Bahía Magdalena, Baja California Sur. 20 records from Données du/de la naturaliste Branger Fabien provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Données espèces - Expertise IPE 79. 615 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 24005 records from NBIS Records to December 2016. 84 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an-Calakmul, México. 2 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 5 records from Rohrmeistereiplateau und angrenzendes Gebiet. 2 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 22 records from Finchingfield Brook historic river corridor surveys. 4 records from South American Antarctic Marine Biodiversity Literature. 744 records from Arizona State University Vascular Plant Herbarium. 280 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 24 records from Données naturalistes de MOREAU Patrice. 1 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 3 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 358 records from Trawl-survey data in the central-eastern Adriatic Sea (Mediterranean) collected in 1957 and 1958. 5 records from California State University, Long Beach Birds. 6 records from Naturmiljø Bergensbanen 2015 (project number 616033). 2 records from Données espèces - Expertise IPE 70. 31 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 4 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 3278 records from Observations naturalistes des Amis de BioObs.. 1 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 53 records from Biogeography of near-shore reef fishes in northern New Zealand. 1101 records from Inventaire de la flore de Gironde 2015. 8 records from Données naturalistes d'Aurélie CHEVILLON. 3 records from Steinbruch Mainz-Weisenau, 2. Jahr. 267856 records from Anillamiento SEO_Bird ringing. 26 records from NE Scotland other invertebrate records 1800-2010. 490 records from Geneva Herbarium – General Collection (G). 53 records from NE AVH data. 1 records from Birdrace-Di_Bi_Di_Birder-Wesel. 71 records from Vascular plants of the Valleys of Hell, Danniye-Akkar, Lebanon, 2019. 3 records from Inventaires tous taxons réalisés pendant l'année 2014 le long de la Petite Ceinture à Paris. 1 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 5 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1367 records from QLD DERM Coastal Bird Atlas (Trial). 3 records from Deponie Klausdorf. 1 records from Birdrace-Die_Laufenten-Braunschweig. 43 records from Données Entomologiques A. HORELLOU 1988-2018. 1 records from Aktion - Friedensburg Oberschule. 2 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 1 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 57 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 16 records from Erlengraben/Lipp-Tal (Östringen). 2 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 1851 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 29 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 51 records from Terrestrial avian occurrences in the context of urbanization of Central Chile. 6 records from Colección de peces del Museo de Historia Natural de la Pontificia Universidad Javeriana. 162 records from Iowa State University Fishes Collection. 2 records from EDIT - ATBI in Gemer area (Slovakia). 40 records from Macrobenthos monitoring in function of the Water Framework Directive in the period 2007-2009. 98 records from Inventaire de la flore du PNRLG 2014 (Landes et Gironde). 5 records from Teich Berlin Wuhlheide. 1 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV4. 1 records from Pollen record of profile L11. 9754 records from Natural History Museum (London) Collection Specimens. 1 records from Ried und Sand - Artenvielfalt durch Beweidung. 3 records from AKG-Gelände (Bensheim). 531 records from Flora Atlas N.T.. 1 records from Biotope im Schulumfeld. 3 records from Fishes in the Argentine Sea from 1967 to the present time. 1 records from Herbaceous and arboreous plants list on the Komaba Campus of University of Tokyo, Japan. 1293 records from Cawthron Institute freshwater invertebrate data. 2 records from WOLL AVH data. 11 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 2 records from TULGU Herbarium: Tula Oblast collections of vascular plants. 3 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 3 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 2 records from Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Colección de Peces de Agua Dulce del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 5306 records from Jordal. 47 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 1 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1 records from Förderzentrum Schmölln. 25 records from Collection botanique Jaubert et Saul (BOUM). 3 records from Fish distribution data, Mayor Is. (Tuhua) marine reserve 1993. 4 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 1 records from Données 2014 de l'Observatoire de la Biodiversité des Forêts. 6 records from Lebensraum Gesamtschule (Langerwehe). 1 records from Artenvielfalt auf dem Schulgelände. 159 records from Neptune Deep-Sea Microfossil Occurrence Database. 894 records from DMNH Birds. 12 records from BenthosChukchiFN762_1976_Falk5. 9 records from National Museum of Natural Science. 39 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 2 records from Collection tropical liverworts serving as vectors for symbiotic fungi at the Staatliches Museum für Naturkunde Stuttgart. 4 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 16 records from AMAPPS Northeast Shipboard Cruise Summer 2011. 23 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 1 records from BIRDRACE Pfeifenten. 4 records from Données du/de la naturaliste Gourlin Benjamin provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Marine metagenome ICM_JRV. 270 records from Insects from light trap (1992–2009), rooftop Zoological Museum, Copenhagen. 3 records from Collections ichtyologiques et herpétologiques (BOUM). 4 records from Knechtweide (Kohlfurth). 73 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 128 records from Données naturalistes de Bruno OGER. 225 records from Aves migratorias boreales y australes en un bosque secundario con algún grado de intervención (Jardín Botánico) y en una zona periurbana (Campus Barcelona, Unillanos) de piedemonte, Villavicencio, Meta.. 1 records from Collection Gilles Becquet (BOUM). 6 records from Meniscus Midges (Dixidae) of Ireland. 5 records from Census of waterbird in Benin Flyway. 228 records from Total phytoplankton inventory in the Southern Bight of the North Sea between 1973 and 1974. 1 records from Alien Species in Poland - Animals. 3 records from Occurrence database of native plants and animals of south-central Chile. 3 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 2 records from NE Scotland fish records 1800-2010. 4 records from BIRDRACE Asiola-Quartett. 2 records from Northern Biodiversity Program Coleoptera (2010-2011). 1 records from Natura 2000 Parc naturel régional de Lorraine. 2394 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 3 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 20 records from UF Florida Museum of Natural History Mammals. 2 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 10 records from National Museum of Marine Biology and Aquarium. 409 records from Invertebrate collections, UiB. 1 records from Pollen profile ADR353. 1752 records from Kenya Bird Map (Full protocol and Adhoc records). 29 records from Vascular plants of south-central China. 1 records from Ecological study of the fish fauna near the mouth of the Zwin in 1985 and 1986. 3 records from Poliquetos litorales de la región norte y centro del estado de Veracruz. 3 records from BIRDRACE Punkbirder Helgoland. 1 records from Bulletin de la Société d'Histoire naturelle de Colmar. 247 records from Coleoptera collection, NHM. 45 records from Biodiversidad íctica de la Isla Cayos de Albuquerque Reserva de Biosfera Seaflower-Proyecto Colombia BIO. 1 records from Naturpark Kottenforst-Ville 18.6.09. 3 records from Données du/de la naturaliste BREARD Jean provenant de la base de donnée du SINP Île-de-France CETTIA. 23 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 6 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 4 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2015. 4 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 76 records from DDT05_2017_12_18. 1 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 2 records from Mosses and Lichens (Vermorel coll.). 9 records from Abundances and biological traits of fish sampled by electrofishing (except specific abundance indices) on the River Oir since 1988 (France).. 30 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 44 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 2 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 248 records from Butterflies of Ireland. 1 records from Artenvielfalt auf Zollverein. 17 records from Données des collections d'algues du MNHN. 1 records from Nottingham Urban Wildlife Scheme iRecord download 2014 - 2017. 15 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 1904 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Entomological Collection. 4266 records from NOAA AFSC North Pacific Groundfish Observer. 4 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 476 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 12 records from Caracterización de la avifauna en una zona delimitada entre los municipios de Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño). 24 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 25 records from Glasgow Museums BRC: Carabidae. 13 records from Aves de la Ecoreserva Predio ASA (Acacias, Meta) - Proyecto FIBRAS. 1 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 552 records from CAS Invertebrate Zoology (IZ). 3 records from water Raw sequence reads. 39 records from The Fungal Collection at the Botanische Staatssammlung München. 140 records from Phanerogamic Botanical Collections (S). 966 records from Insects, Outer Hebrides. 9 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 9 records from Herbarium specimens of Hokkaido University Museum. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 39 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 312 records from BioGIS - Vascular plants - Israeli Gene Bank. 234 records from Desert Botanical Garden Herbarium. 91 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 9 records from Gurgltal (Tarrenz). 12 records from CNCR/Colección Nacional de Crustaceos. 242409 records from Line transect censuses of breeding birds. 1 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 2 records from Dipterists Forum: Field Week 2002 (Inverness). 128 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 6 records from Marine metagenome ICM_WBS. 1 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 37 records from Colección Ornitológica de la Universidad del Valle. 79 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 6 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 6 records from Données du naturaliste Danten Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008. 960 records from Flora d'Andorra. 573 records from Florida Fish and Wildlife Conservation Commission - Freshwater Fishes of Florida - 1956-2000. 49 records from REDIT 1. 998 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 1 records from Données rhopalocères. 10 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, méxico. 3556 records from Standing Waters Database - Scotland. 8 records from Données faune ZNIEFF de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS. 36 records from Censo de aves en el Santuario de Flora y Fauna Guanentá Alto Río Fonce para el periodo 2011 a 2013. 7 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 1 records from Données naturalistes de Renaud PUISSAUVE. 7377 records from Dry Tortugas Reef Visual Census 2010. 696 records from MijnVISmaat - Exotic fish occurrences in Belgium. 50 records from University of Guelph Insect Collection (DEBU). 1 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 1 records from Marine algal (seaweed) flora of Faial Island, Azores. 285 records from SBBG - Clifton Smith Herbarium, Santa Barbara Botanic Garden. 2 records from Naturgrundstück (Eutin). 2 records from Truppenübungsplatz Panzerkaserne Böblingen. 14 records from DFO Pacific Groundfish Synoptic Trawl Surveys - Strait of Georgia. 24 records from Red Sea microbial plankton Raw sequence reads. 47 records from Development and validation of a multi-trophic metabarcoding biotic index for benthic organic enrichment biomonitoring using a salmon farm case-study.. 1720 records from Florida Keys Reef Visual Census 1996. 62 records from Ulster Wildlife ShoreNI iNaturalist records. 227 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 15 records from Records from the RHS insect reference collection. 301 records from Données de l'Observatoire de la Faune de Bourgogne. 35 records from MACF - MacFadden Herbarium, California State University Fullerton. 137 records from Inventaire de la flore de Bordeaux Métropole 2013. 24 records from Phenological Center - Birds (Murmansk). 1 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 111 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 3 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 1 records from Echinoderms from the Seaflower Biosphere Reserve. 4 records from If_Ecologie_Conseil_2017_12_18. 53 records from ARKO strandeng. 1655 records from Inventaire de la flore de Dordogne 2016. 505 records from Allan Herbarium (CHR). 315 records from Inventaire de la flore des Landes 2014. 403 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Plantas Tapachula). 35 records from A grid-based database on vascular plant distribution in Samoylovsky District of Saratov Oblast, Russia. 3 records from Klutensee. 20 records from Meiobenthos of the Dutch Continental Shelf in spring 1991. 72 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE272. 1 records from verschiedene Kleingewässer um Oldenburg/Holstein. 1 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 6 records from Ornithological observations in the Kharkiv region of Ukraine. 125 records from Distribution and community structure of benthic copepods in the Delta area and the Ems-Dollard between 1976 and 1981. 13 records from CAS Entomology (ENT). 1635 records from Carnet B Lorraine. 53 records from Naturalis Biodiversity Center (NL) - Pisces. 6 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 701 records from Canadian Museum of Nature General Invertebrate Collection. 95 records from Historical landings from the Rijeka (Croatia) fish market between 1914 and 1932. 472 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 3729 records from Seasearch Marine Surveys in England. 1 records from Collection des Mollusques (BOUM). 3 records from HSS-carpoteca (HSS-C) Finca La Orden-Valdesequera (CICYTEX). Junta de Extremadura. 8 records from Annales de la Société Linnéenne de Maine-et-Loire. 3 records from Comunidad íctica del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 39 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 1 records from BIRDRACE Kollektiv Eisente. 1 records from Données du/de la naturaliste ESSAYAN Roland provenant de la base de donnée du SINP Île-de-France CETTIA. 66 records from Collection Trichoptera - SMF. 2 records from Eyre Peninsula's Bird Monitoring Program. 171 records from Insectes Hétéroptères Mirides de France. 1 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 13 records from Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 940 records from Phase Two Lowland Heathland Survey. 2484 records from NOAA Pacific Islands Fisheries Science Center, Ecosystem Sciences Division, National Coral Reef Monitoring Program: Stratified random surveys (StRS) of reef fish in the U.S. Pacific Islands. 9 records from Peces exóticos invasores en la región hidrológica prioritaria Río Amacuzac, Morelos. 680 records from BLS Mapping Scheme dataset, 1750-2009. 35 records from Arizona State University Hasbrouck Insect Collection. 15996 records from USGS Great Lakes Science Center Research Vessel Catch Information System Trawl. 42 records from Base de datos sobre ictioplancton para la Bahía de Campeche, México. 1 records from Plantas de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 2 records from Streuobstwiese. 1 records from Collection Vermes - ZMB. 5 records from Caracterización y monitoreo de fauna silvestre en el área de influencia directa de Hidrocasanare- Yopal del 2014 a 2017. 399 records from Western Australian Museum provider for OZCAM. 1 records from BIRDRACE - The famous Grouse feat. The James. 15 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 1 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 41 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 3 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 15 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 14696 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 4747 records from NRW Regional Data: South East Wales Non-sensitive species. 83 records from CMC_herpetology_vouchers. 14 records from UNCW Marine Mammal Sightings 2001. 6 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 1 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 7498 records from Waarnemingen.be - Non-native plant occurrences in Flanders and the Brussels Capital Region, Belgium. 3 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 110 records from Inventaire de la flore du Grand Poitiers 2009. 7 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 2 records from Inventaire de la faune de vertébrés du Parc national du Mercantour. 8 records from Colección Mastozoológica de la Universidad Industrial de Santander. 2 records from Schulhof Gymnasium Hürth Bonnstrasse. 5 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 1 records from BIRDRACE Bon(n)apartemöwen. 10 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 1892 records from natagora-earlybirds. 1 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 11 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 3 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 2 records from Renaturierung Werse (Innenbereich Beckum). 8 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 12 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 27 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 214 records from Midden-Limburg Fish Ponds Survey. 11 records from Dataflos. 275 records from UTEP Plants (Arctos). 15 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 1 records from Herbarium Senckenbergianum (FR) - Fungi. 39 records from National System of Protected Areas in Poland - Animals. 10 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 23 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 12 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 97 records from AMAPPS Northeast Aerial Cruise Summer 2016. 3 records from WADFW PSAMP S1992. 31 records from Geometridae de France métropolitaine. 56 records from Línea base general de aves para el valle medio del Magdalena - VMM. 50 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 5 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 1 records from Bad Bodenteicher Heide. 423 records from Grassland Survey of Lochaber 1990-94. 20 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 2 records from South Lanarkshire peatland records 2013. 16 records from MAC herbarium - Instituto do Meio Ambiente do Estado de Alagoas - Herbário Virtual REFLORA. 1 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 2 records from Inventaire des oiseaux sur le territoire de la métropole Rouen Normandie. 45 records from PondNet data 2012-2014. 17 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 4 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 1931 records from First Bird Atlas. 11 records from Monitoring scheme of birds and mammals that are visiting bird feeders during winter. 57 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 117 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from The Fish Sampling at Lata Fish Market in Temotu Province, Solomon Islands. 3 records from New and additional records of hyperiidean amphipods of the infraorder Physosomata (Crustacea: Amphipoda: Hyperiidea) from the Antarctic Zone of the Southern Ocean. 49 records from MMS Marine Mammal Survey, PNW 1989-1990. 1 records from Field Museum of Natural History (Action) Mammals Sightings. 49 records from Ibaraki Nature Museum, Vascular Plants collection. 12 records from Fungi (S). 135 records from Inventaire de la flore de Charente-Maritime 2018. 162 records from Alien macroinvertebrates in Flanders, Belgium. 108 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 10 records from Pollen profile RAC20, Lake Racou, France. 1 records from BIRDRACE Resopal-Darmstadt-Dieburg. 38 records from NCSM Mollusk Collection. 120 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 2 records from Baltic Seabirds Transect Surveys. 5 records from SNH Invertebrate Site Condition Monitoring 2015: Perchhall Loch SSSI. 5 records from Fishes of water bodies of Rzhyshchiv town amalgamated territorial community (CATC) 2021. 3 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 49 records from Natura 2000 Vallée de la Seille. 2 records from VSN-Wiese. 7 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 1 records from Données naturalistes d'Amélie TINAT. 32 records from Données naturalistes d'Anita GEORGES. 83 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 5 records from Umgebung der Gesamtschule Winterhude (Hamburg). 565 records from Insect Collection of Saitama Museum of Natural History. 54 records from Local BioBlitz Challenge 2013. 53 records from Ecological study of the plankton in the port of Ostend in 1965. 3 records from Alien plants of Sterlitamak. 346 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 20 records from Tidlig oppdagelse og varsling av fremmede arter 2020. 39 records from Données naturalistes de Arnaud HORELLOU. 43 records from Australian Antarctic Division Herbarium. 141 records from Bryophyte diversity in forests. 15 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 1 records from BIRDRACE Nachtigallen. 3 records from Triebesbach (Zeulenroda-Triebes). 271 records from Norfish: English North-East Atlantic cod fishery, 1520-1790. 3361 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 613 records from Inventaire de la flore de Lot-et-Garonne 2017. 442 records from Trondheim urban biodyversity survey. 37 records from BIOLOGICAL SCIENCES DATA. 184 records from Florient - a database dealing with historic wild plant occurrences. 17 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2005. 1 records from Wiese und Weide am Waldrand von Gusterath. 2 records from BLS Lichen Database: Wales churchyards 1700-2016. 5 records from Unna-Mühlhausen, Wiesen. 7 records from IBF Monitoring of Plant Galls. 23 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 1 records from Birds Specimens of Akita Prefectural Museum. 4 records from Schulaktion des Dienzenhofer-Gymnasiums. 134 records from UAM Fish Collection (Arctos). 3803 records from niek_2022. 3002 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81. 11 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 7 records from Rare vascular plant species of Transbaikalia (Republic of Buryatia and Zabaikalsky Kray), Russia. 1 records from Inventaire de la flore de Charente 2014. 15 records from Royal Belgian Institute of Natural Sciences Cnidaria collection. 61 records from AMAPPS Northeast Aerial Cruise Summer 2011. 10 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 10088 records from Natural Resources Wales Regional Data : Mid-Wales. 49 records from Données Saint-Gobain Distribution Bâtiment France. 4 records from ERBG AVH data. 816 records from River Biologists' Database (EPA). 1 records from Selztal bei Friesenheim. 1 records from Great Eastern Ranges - Slopes to Summit. 3467 records from Tiroler Landesmuseum Ferdinandeum. 6037 records from Data collected on citizen science web portal www.ornitho.cat. 2 records from Tongrube bei Hettstedt. 11073 records from Swedish Bird Survey: Fixed routes (Standardrutterna). 4158 records from Vascular plant herbarium TRH, NTNU University Museum. 5 records from Quarrendorfer Landschaftsschutzgebiet. 23 records from Vascular Plant Specimens of the RYU Herbarium (Faculty of Science, University of the Ryukyus). 39 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 1 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 6 records from Records of the Australian National Botanic Gardens Seedbank. 9 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 169 records from Programa Poseidon - Citizen Science Project Results. 4 records from Transferts SI Faune - Données naturalistes opportunistes de Sylvain BONIFAIT. 283 records from Freshwater fishes of Serbia and Montenegro. 32 records from BLM CETAP OPP Sightings. 3 records from Données naturalistes de Pauline BALDUCCI. 36 records from Gunma Museum of Natural History, Insect Specimen. 137469 records from Swiss National Databank of Vascular Plants. 43 records from South East Scotland Tetrad Atlas 2007 - 2013 - non-sensitive winter species. 775 records from DIBA-Parc del Montnegre i el Corredor. 907 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 2 records from MoJ BioBlitz August 2018. 583 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 18 records from USFS - New York City Tree Census - 1995. 394 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 1 records from JRS Wetands data Rwanda, 2019. 1 records from Werl macht sich auf die Suche. 118 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 21 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 3477 records from UF FLMNH Ichthyology. 2 records from Vegetation of the tidal channels in Gazi Bay (Kenya) sampled between July and September 1989. 41 records from Fish Collection of National Museum, Philippines. 6 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 310 records from Inventaire de la flore de Charente-Maritime 2017. 2 records from Vegetation and ecology of tidal marshes in the Zwin (Knokke-Heist, West-Vlaanderen). 280 records from Moss occurrences in Yugyd Va National Park, Subpolar and Northern Urals, European North-East Russia. 60 records from Mammals Specimens. 1 records from Birkenpilz. 182 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Aves). 33 records from Lauri Mällo private collection of Lepidoptera. 3 records from UCM Bird Eggs/Nests Collection (Arctos). 265 records from Trawl-survey data from the “expedition Hvar” in the Adriatic Sea (Mediterranean) collected in 1948-1949. 14 records from Formación de las colecciones de referencia de aves y mamíferos de la Reserva de la Biosfera de Sian Ka'an, Quintana Roo, México. 240 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 17 records from CSIRO, Jack Mackerel surveys, 1978. 1 records from Weidegut Rechab. 5 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 1999. 5 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 76 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 137 records from National System of Protected Areas in Poland - Plants. 1 records from Condon Fossil Collection - Oregon Museum of Natural and Cultural History. 131 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, November 2017-October 2018. 6 records from University of Cincinnati, Margaret H. Fulford Herbarium - Vascular Plants. 140 records from Données du naturaliste Maxime Zucca provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Bryophyte diversity in grassland. 41 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 6 records from Reptiles y aves del Distrito Nacional de Manejo Integrado Cabo Manglares Bajo Mira y Frontera, Pacífico colombiano - Proyecto Colombia BIO. 3 records from Aves de la Ecoreserva La Tribuna (Neiva, Huila) - Proyecto FIBRAS. 12 records from Phytoplankton abundance in surface water in October 1997, Chimbote, Peru. 76 records from New Zealand Biodiversity Recording Network. 19 records from Données du naturaliste Doux Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from NW pacific deep-sea benthos distribution and abundance (Beneficial Project). 10 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 4 records from Données du naturaliste Christian Desmier. 5 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 7 records from SMNS Herpetologie. 334 records from Underwater fish visual census in the Azores from 1997 to 2015. 272 records from Norfish: Norway Cod Fishery 1520-1791. 2 records from Birdrace-Team_Havelland-Havelland. 147 records from Sizing Ocean Giants. 14 records from Avifauna asociada a paisajes rurales degradados en la vereda San Luis, Barrancabermeja - Santander. 7 records from Biodiversidad asociada a la declaración del Área Protegida en el Pueblo Indígena EPERARA SIAPIDARA, Resguardo Calle Santa Rosa, Timbiquí (Cauca). 157 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 3 records from Prophetensee Quickborn. 13123 records from SEWBReC Birds (South East Wales). 30 records from Monitoring of the effects of Belgian wind mill parks on benthic macro-invertebrates and the fish fauna of soft substrates - reference situation. (WINMON). 1 records from Luderbusch. 8 records from Données du naturaliste Alexandre Mari. 9 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2016. 2 records from Die Teiche im Britzer Garten. 55 records from Lepidoptera of Mordovia State Nature Reserve. 12693 records from Ringing or Bird Recapture. 39 records from Findings of insects on the territory of Rzhyshchiv city amalgamated territorial community (CATC) in 2020-2021 and earlier years. 193 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 404 records from Weed plants of the European part of Russia. 2380 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 39 records from Fish Collection of Yokosuka City Museum. 9 records from Dipterists Forum: Field Week 1981 (Kent). 2 records from MEXU/Flora de Oaxaca. 13172 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 93 records from Eulachon migration bottom trawl surveys. 436 records from MARINe/PISCO: Intertidal: MARINe Long-Term Monitoring Surveys: Sea Stars and Katharina. 316 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 1 records from SNH Invertebrate Site Condition Monitoring 2015-16: Den of Airlie SSSI. 163152 records from Pl@ntNet automatically identified occurrences. 117 records from Noctuoidea de France métropolitaine. 43 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 2 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 5 records from Données du/de la naturaliste Provost Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Wirbach-Taubental (Bad Blankenburg). 15 records from Données naturalistes d'Alain BERLY. 12 records from Universidad del Valle de Guatemala - Colecciones Biológicas - Aves. 3 records from Données espèces - Expertise IPE 120. 11 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 10 records from Ville de Trois-Rivières - Bioblitz 2012. 101 records from LSUMZ Birds Collection. 1713 records from Fauna Atlas N.T.. 9 records from Inventaire de l'îlot du Lédénez Vraz. 1 records from Données opportunistes. 29 records from Bird survey with mapping at the permanent sample plots in the Prioksko-Terrasnyi Biosphere Reserve. 56 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 62 records from Yoann_BLANCHON_2017_12_18. 13767 records from Données de la flore d’Alsace (SBA). 1 records from BIRDRACE Brut. 2 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 105 records from 2019_nsmk_biodiversity_pi_5774. 1 records from Birdrace-Buteo2DO-Dortmund. 8 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 8 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 21 records from Données naturalistes de Monsieur Le Cesne Maxime. 11 records from DREAL Auvergne - Insectes - 2015. 98 records from Données naturalistes de Cédric JACQUIER. 67 records from Catalogue of the plant communities of Madeira and Porto Santo. 9 records from Biodiversidad asociada al proyecto Línea de Transmisión de Energía Segundo Circuito San Lorenzo - Calizas a 110 kV, Antioquia. 29407 records from Observations floristiques floutées issues de la base de données flore du Conservatoire botanique national alpin. 24 records from Occurrence of the birds of the Middle Volga Region (South-East of the European part of Russia). 14 records from NatureShare. 2337 records from TUR Vascular plant collections of the Turku University, Herbarium generale. 495 records from Inventaire de la flore des Landes 2012 (Chalosse et Tursan). 9 records from Données naturalistes du Comité départemental de l'Essonne (CODEP91) de la Fédération Française d'Etudes et de Sports Sous-Marins. 9 records from Données espèces -Expertise IPE 76. 96 records from University of Minnesota Insect Collection. 6 records from Heinersdorfer Sumpfwiese. 22 records from Actualización del conocimiento de la diversidad de especies de invertebrados marinos bentónicos de aguas someras (<50m) del Sur del Golfo de México. 7 records from Naturerlebnisraum Koppelsberg. 441 records from Arctic Species Trend Index (ASTI) : Marine. 2 records from Données de la Ville de Colombes provenant de la base de donnée du SINP Île-de-France CETTIA. 28 records from Seabird Observations, Storm Bay, Tasmania, Australia, 1991-1994. 1 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 887 records from MLZ Bird Collection (Arctos). 2 records from Bernhardsthal. 1 records from Données naturalistes de Monsieur VINCENT Alexis. 4 records from Naturschutzgebiet Müchelholz (Mücheln). 4 records from Wiese am Waldrand (Gurtweil). 2 records from Birdos along the Greenway. 39 records from Fish and crustacean community in the Western Scheldt (Doel nuclear power station) during winter season 1991-1992. 1 records from NSW South Coast & ACT plants. 3 records from Inventaire "Espaces Naturels Sensibles" de Marthe (SAINT-SEVER-MONTGAILLARD). 1 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 112 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 15 records from Clémence Lortet herbarium. 2 records from Jardin botanique de Montréal (JBM). 51 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 903 records from SHARK - National phytoplankton monitoring in Sweden since 1983. 3 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 7 records from Pöhlberg bei Annaberg. 361 records from NHMD Ornithology Collection. 2 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 1 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 1 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 2 records from Composition and genetic diversity of picoeukaryotes in subtropical coastal waters as revealed by 454 sequencing-by-synthesis. 9303 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 19 records from SWECO. 8 records from Données naturalistes de Loïc SALAUN. 599 records from Bird records for Argyll for the years 2002 and 2003. 1 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 73 records from nsmk_fish_biodiversity_2019. 143 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 17 records from CSIRO, Cruise SS200702, Marine Biodiversity Survey, Southeast Australia, 2007. 39727 records from Flore Franco-Belge. 7 records from East Ayrshire Species Database. 16 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 298 records from Marine Biological Sample Database, JAMSTEC. 234 records from Irish Whale and Dolphin Group. 7 records from The Nanoeukaryotic plankton Raw sequence reads. 1 records from Birdrace_Deutschlands_enthusiast.Vogelkucker-Münster. 5 records from Données espèces - Expertise IQE 308. 8 records from Données espèces - Expertise IQE 95. 6 records from The Taiwan Breeding Bird Survey Data. 50 records from Collection Crustacea - ZMB. 125 records from The Living Murray Fish data. 1031 records from Observations.be - Non-native species occurrences in Wallonia, Belgium. 2 records from Gemeinschaftsgarten Deluxe (Bernburg). 4 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 18 records from Censo de aves en el Santuario de Fauna y Flora los Colorados en el periodo 2008 a 2012. 1074 records from Inventaire de la flore des Pyrénées-Atlantiques 2015. 11 records from Schatzinsel Norderney. 614 records from Freshwater fishes of Poland. 38 records from Long-term Bird Census in Cigu 2004-2017. 75 records from Programa de fotomonitoreo de objetos de conservación y amenazas en el Sistema Nacional de Áreas Silvestres Protegidas del Estado (SNASPE). 6386 records from Carabidae records for Britain to 2014. 1 records from BARTH-Environnement_2017_12_18. 292 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 19 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 138 records from INNS Data: All Taxa (South East Wales). 1 records from Données rhopalocères de Inge VAN HALDER. 18 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 203 records from MVZ Egg and Nest Collection (Arctos). 1 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 1 records from Overvåking Røsskleiva NR. 355 records from The national database for marine data (MADS). 15804 records from CSIC-Real Jardín Botánico-Anthos. Sistema de Información de las Plantas de España. 393 records from VIS - Non-native fish in Flanders, Belgium. 1 records from UNCW Hatteras Aerial Survey -Left side- 2017. 1 records from Kabelskebach (Kabelsketal, Saalkreis). 4 records from Adenda a la colección de referencia de invertebrados de la Estación Mazatlán, UNAM y análisis de la fauna de crustáceos isópodos del Pacífico mexicano, julio 1996-julio 1997. 26 records from European riparian ground beetles. 8 records from Freshwater Macrophyte Survey Data. 1 records from BIRDRACE Enger am Spektiv. 126 records from Taxon occurrence data for the FungalRoot database. 9 records from Gelände des IVL (Zeckern). 109 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 29625 records from Hawk Migration Association of North America - HawkCount. 4418 records from Florida Keys Reef Visual Census 1997. 13 records from Swedish Bird Survey: Swedish coastal bird monitoring programme (Nationella kustfågelövervakningen). 1 records from Coleção de Mamíferos da Universidade Estadual do Norte Fluminense. 1 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 39 records from CSLA - Cal State LA Herbarium. 712 records from E. C. Smith Herbarium (ACAD). 722 records from RSA - California Botanic Garden Herbarium. 39 records from LA - University of California, Los Angeles Herbarium. 160 records from Alterra (NL) - Entomofauna inventory in peat swamps. 742 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 16103 records from EBCC Atlas of European Breeding Birds. 8214 records from Florida Keys Reef Visual Census 2010. 26 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 8 records from Leicestershire and Rutland Mature trees Inventory 2011. 21 records from Données diverses du Parc naturel régional de Lorraine. 1 records from Arabian sea sediment samples with protist reads Metagenome. 61 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 32 records from Census of bird species carried out in Ramsar 1018 and 1017 sites of Benin. 15 records from Subtidal macrobenthos monitoring in function of a foreshore suppletion at the Belgian coast, period 2013-2016. 6 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 34 records from Bioimages. 4 records from Extracellular DNA marine sediment Targeted Locus (Loci). 1 records from Draubiotop Lavamünd. 73 records from Données RNF - PNR des ballons des Vosges. 4 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 275 records from Northern Gulf of St. Lawrence Fishes. 6 records from "Schwarzwassertal" bei Pobershau. 3 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 2 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2008. 895 records from Museums Victoria provider for OZCAM. 210 records from Duke University Herbarium Algae Collection. 1 records from marine metagenome Targeted Locus (Loci). 604 records from Plan de vertebrados de la Patagonia. 1 records from Birdrace_TerraCamper-Münster. 98 records from SysTax - Zoological Collections. 70 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 3 records from AlgaTerra. 10 records from 2019_nsmk_pl_3. 1 records from LTB AVH data. 3704 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 86 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 15 records from Danielsberg (Mölltal, Kärnten). 2 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 5 records from LPO_PACA_2017_12_18. 8 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 38 records from Birds of Cisna Community (southern Poland). 66 records from Données naturalistes hors Île-de-France saisies dans Cettia-idf. 16 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from DBRC Trichoptera 1974 - 2015. 32 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 5 records from Collection Malakologie - SNSD. 5 records from 2019_NSMK_PL_2. 3 records from Observations de Daniel Robin. 5 records from Arizona State University Lichen Herbarium. 10 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 404282 records from INPN - Données flore des CBN agrégées par la FCBN. 1010 records from Seabirds of the Southern and South Indian Ocean. 1 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 69 records from Observatoire Pelagis boat surveys 2003-2021. 13 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 2 records from Informatisation des carnets de terrain de Georges Catherine. 3350 records from Atlas de las Aves de México: Fase II. 316 records from WTSWW Data: All Taxa (West Wales). 1005 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 6 records from Données espèces - Expertise IPE 10. 311 records from South Australian Museum Australia provider for OZCAM. 567 records from Seasearch Marine Surveys in Ireland. 12 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 252603 records from DOF - Observations from the Danish Ornithological Society. 108 records from Communities of ground beetles (Carabidae, Coleoptera) in broad-leaved forests of protected and urban areas of the Kaluga Oblast (European Russia). 1 records from Brock University Herbarium (BU). 17 records from Flore Bord de route/CG55 - Parc Naturel régional Lorraine. 34 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 78 records from SIO Benthic Invertebrate Collection. 2427 records from Marine Commercial Fish Survey (FV Kapala, FV Trader Horn, FV Shelley, FV Kirrawa, FV May Bell) in the East and South East Australian Region from 1975 to 2008. 86 records from DASSH Data Archive Centre volunteer survey data. 4010 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 2 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 78 records from NEFSC Aerial Circle-Back Abundance Survey 2006. 2 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 26 records from BCE butterfly data in and around Nothern Italy. 74 records from Arkansas Natural Heritage Commission Herbarium. 72 records from Cleveland Museum of Natural History. 34 records from HBRG Vertebrates (not Badger) Dataset. 9 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 29 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 2 records from BIRDRACE Immerwiederhopf. 492 records from Murray-Darling Basin fish monitoring survey. 206 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 1753 records from North East Scotland Breeding Bird Atlas 2002-06. 88 records from Modernisation des ZNIEFF du PnrL. 2 records from Benthic Polychaeta (Annelida) from La Paz Bay and Southwestern Gulf of California. 7 records from Composición del fitoplancton de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 2 records from SNH Invertebrate Site Condition Monitoring 2015: Carrick Ponds SSSI. 1 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 352 records from Norfish: Iceland Cod Landings 1520-1871. 75 records from Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 28 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 14 records from Coastal and Marine Species Database. 1 records from Herbarium of Numto Nature Park. 9 records from Convention Fédération française de golf - MNHN 2016-2019.. 2 records from 4. GEO-Tag in Eberbach. 15 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 32 records from Tasmanian Museum and Art Gallery provider for OZCAM. 4 records from Données espèces - Expertise IPE 23. 28 records from GEO-Hauptveranstaltung in "Wildtierland". 23 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 1 records from Raus in die Natur. 7 records from Coral reef-associated fauna in the Bajos del Norte and National Park Alacranes Reef: OCEANA Expedition 2021. 6 records from WIKTROP - Weed Identification and Knowledge in the Tropical and Mediterranean areas. 1 records from Avifauna de los bosques húmedos y remanentes de Tierralta - Córdoba, 2011. 12259 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 611 records from The First Breeding Bird Atlas of Vermont (1976-1981). 4588 records from RU-BIRDS.RU, Birds observations database from Russia and neighboring regions. Zoological Museum of M.V. Lomonosov Moscow State University.. 1 records from BIRDRACE Ohne Graureiher läuft nix!. 87 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 6 records from Avifauna asociada a la ciénega Caño Negro, Medio Baudó, Chocó. 2021. 9 records from CMarZ (Census of Marine Zooplankton)-Asia Database. 1 records from kerkyra. 258 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 8 records from Diversity and composition of preserved angiosperm specimens at Tanzania Forestry Research Institute (TAFORI) Herbarium. 1 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 14 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 423 records from NDFF Butterfly Data. 36 records from Point Count Data for Chaa Creek Lodge, Belize 1997-2001. 1 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 51 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 15 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 4 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 10 records from Aves de la expedición en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 1 records from Brenz (Heidenheim). 7 records from Censo libre de aves en el Parque Amacayacu, periodo 2009 a 2012. 7 records from SO-Polylist. 2 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 8970 records from Localización de táxones botánicos de interés para la identificación de hábitats de la REDIAM (Secretaría General de Medio Ambiente, Agua y Cambio Climático). 25 records from Records of Invasive Non Native Species held on the Cofnod database. 12 records from UKSBA Cyprus Plant Records 2018. 1 records from BIRDRACE Taubenhaucher. 13 records from CUMV Mammal Collection. 29 records from USGS Marine Fishes of St. Croix and U.S. Virgin Islands. 2 records from Collection des données de biodiversité marine de Polynésie française (LAGPLON). 8 records from MHA Herbarium: Collections of mosses from Yana-Indigirka Region, Yakutia, Russia. 2 records from BIRDRACE Kosmos-Racer. 1 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 1 records from Birdrace-Uhulogen-Lippe. 22 records from Collection Aves (bird skins) SMF. 151 records from Données naturalistes de Xavier JAPIOT. 136 records from Série sur le long-terme de Tiahura - Peuplement de poissons. 7 records from BIRDRACE Havelland. 2 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 1 records from Birdrace-SpeedBirder-Zwickauer_Land. 1 records from Birdrace-Die_Vogelscheuchen-Herford. 20 records from Flora of Seymskiy Regional Landscape Park. 225 records from Données du/de la naturaliste Grosso Eric provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from BIRDRACE Vogelscheuchen. 952 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 399 records from Suivi Temporel des Rhopalocères de France (STERF). 1 records from Birdrace-Die_Ornithomaten-Herford. 17 records from Poliquetos criptobentonicos en Orbicella annularis en arrecifes coralinos del PNA de Los Roques Venezuela. 6 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2018. 71 records from NINA Vanndata fisk. 2 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 1 records from Salzwiese Diekskiel. 1 records from Landwehrbach. 216 records from CSIRO, fish surveys by the Soela, 1980s. 1 records from UTEP Insects (Arctos). 8 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 22 records from Leicestershire Bryophyte Data. 219 records from Collection Pisces SMF. 773 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1252 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 16 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 2 records from Données naturalistes de Jean-Jacques BORDE. 59 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 6946 records from Florida Keys Reef Visual Census 2007. 8 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 1 records from Birdrace-Ostseevögel-Ostvorpommern. 4 records from Landschaftspflegehof (Berlin). 1 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 1 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 751 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 2415 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 12 records from DREAL Auvergne - Avifaune - 2015. 16 records from Gemeinde Sursee. 24 records from Données naturalistes de ROMET Nicolas. 1 records from Inventaire de la faune réalisé par Jérôme Fouert. 38 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 2 records from Artenvielfalt auf den Elbwiesen (Dessau). 14 records from Chronicle of Nature - Phenology of Plants of Carpathian Biosphere Reserve. 3 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 51 records from Inventario de Mamíferos Mámbita. 3 records from Lindau im Bodensee. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 2858 records from Estonian Nature Observations Database. 5 records from Naturpark Sternberger Seenland. 708 records from Herbarium Willing at Herbarium Berolinense, Berlin (B). 14 records from Peces de las unidades ecológicas someras Expedición Seaflower Serranilla 2017 - Proyecto Colombia BIO. 38 records from Cowan Tetrapod Collection - Herpetology. 1623 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 5 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 60 records from Insect specimens of Toyota City Nature Sanctuary. 14 records from Sudeniederung (Amt Neuhaus). 1034 records from DFO Pacific Groundfish Synoptic Trawl Surveys - Hecate Strait. 3 records from Hamberger Brücke / Würmtal (Pforzheim). 507 records from Vascular Plant Collection. 6 records from DREAL_PACA_-_N2000_-_Syndicat_Mixte_d'Aménagement_de_la_Vallée_de_la_Durance_2017_12_18. 1133 records from Bryophyte data for Great Britain and Ireland from the British Bryological Society held by BRC: data compiled post-Atlas. 24 records from CASES2003_2004. 444 records from Fife Nature Records Centre combined dataset. 22 records from Flora ficológica marina de Tamaulipas. 1 records from Artenvielfalt im Umfeld der Burgwegschule. 22 records from Vascular plants collection of Hiratsuka City Museum. 3 records from CHAS Botany Collection (Arctos). 554 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 8 records from Universitat de València, Colecciones de Criptógamas: VAL_Briof. 4085 records from IBF Monitoring of Vascular Plants. 163 records from Staten Island Museum. 12 records from Hyperbenthos community in the salt marsh of Saeftinghe in 1990 and 1991. 1 records from Naturschutzgebiet Lochbusch-Königswiesen. 14 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 27 records from Données naturalistes de Philippe GOURDAIN (ANVL). 2 records from BIRDRACE Niederlausitz-Team. 9 records from Cnidaria. 2 records from Schulgarten Huttenheim (Philippsburg/Baden). 9 records from Swedish Malaise Trap Project (SMTP) - Macrolepidoptera. 10 records from Estudio florístico de la Sierra de Pachuca, Hidalgo, México. 14 records from Moluscos Marinhos de Augusto Nobre. 1121 records from The CPR Survey. 7 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 2 records from Vocalizaciones de aves mexicanas en análisis biogeográficos y reconstrucción filogenética. 82 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2015. 31 records from Inventaire et suivi Avifaune. 5 records from Botanic Garden of the Finnish Museum of Natural History. 71 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 4 records from Colección Herbario Federico Medem Bogotá - FMB. 109 records from Epibenthos and demersal fish monitoring in function of dredge disposal monitoring in the Belgian part of the North Sea. 6 records from SNH Invertebrate Site Condition Monitoring 2013/14: River Spey - Insh Marshes SSSI. 2 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 171 records from LACM Invertebrate Paleontology. 1 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 5 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 4 records from Faberpark (Nürnberg/Stein). 2 records from Monitoreo de aves por medio de transectos libres en el Parque Nacional Natural Cueva de los Guácharos en el 2019. 4 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 1279 records from Whimbrel Tracking in the Americas (aggregated per 1-degree cell). 38 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 2 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 1998 records from Database for alien invasive plants occurrences in Germany. 47 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 1042 records from North East Scotland Invasive Non Native Plants. 2 records from Tornoer Teich. 1 records from Birdrace-NAJU_Aspach-Rems/Murr. 20 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 3 records from 成龍溼地鳥類生態紀錄. 2 records from Données du/de la naturaliste Sarouille Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Berlin-Brandenburg Plant Collection 2006. 8 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 30 records from SEFSC Southeast Cetacean Aerial Survey 1992. 6480 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 283 records from Parc_National_du_Mercantour_2017_12_18. 6 records from OUPR - Herbário "Professor José Badini". 1017 records from CEDaR Online Recording. 2 records from Inventaire Faune Flore du Cirque de l'Essonne. 1 records from BIRDRACE Die Laufenten. 395 records from Données naturalistes d'IFRECOR (pf). 182 records from National Biodiversity Data Bank. Observation records, 1900-2014. 6071 records from Florida Keys Reef Visual Census 2006. 1 records from Schellenberg A. 1936. The fishery grounds near Alexandria. Amphipoda Benthonica. Notes and memoirs No 18.. 1039 records from MHA Herbarium: collections of vascular plants. 1 records from Occurrence database of bryophytes and native animals of southern Chile. 272 records from BLS Lichen Database: England 1650-2016. 2094 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 13 records from Vascular plant specimens of Sugadaira Research Station, Mountain Science Center, University of Tsukuba. 8 records from California State University, Long Beach Mammals. 273 records from CDA - California Department of Food and Agriculture. 14 records from Royal Saskatchewan Museum - Ichthyology Collection. 37 records from Insect Collection (CeStuBio). 2 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 821883 records from Bird Ringing Centre in Sweden (NRM). 1 records from Nottekanal, Klasse 7 - 10. 12 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Pisces (ZUFMS-PIS). 17680 records from Swiss National Moths Databank. 23 records from Actualización y depuración de la base de datos del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. Fase 2. 1 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 14707 records from RECORD Vascular Plant Data. 2 records from Mamíferos pequeños asociados a las cuencas abastecedoras del embalse La Fe en el departamento de Antioquia. 14 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 8 records from Harpacticoida from a scientific cruise of the R. "Akademik" in the western part of the Black Sea. 6 records from SCFS - Sagehen Herbarium. 29 records from NDFF Wall Plants Monitoring Program. 1846 records from Atlas des poissons d'eau douce de France métropolitaine (2011). 2 records from sediment metagenome Metagenome. 19 records from Estudios previos justificativos para la declaratoria de áreas naturales protegidas en Tamaulipas. 528 records from Données naturalistes de Pascal Dupont. 4 records from Woodmeadow Invertebrate Survey 2019. 2 records from Blumenrather Heide / Virneburg. 5 records from Description of a new genus and species of Chrysopetalidae (Annelida: Polychaeta) from the NE Atlantic, with some further records of related species. 4441 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 24 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 4606 records from Marine benthic dataset (version 1) commissioned by UKOOA. 2 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 4 records from Aerial Oil Spill Response Survey 1994-1997. 37 records from Freshwater Fishes of Bulgaria. 17 records from Colección de Plancton Mixto – Sección Fitoplancton del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 127 records from European Moth Nights. 9 records from Invazivke - Invasive Alien Species in Slovenia. 2 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 25 records from Coleção de Crustacea do Museu Nacional (MNRJ - CARCINO). 4 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 30 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 505 records from NBMB Herps. 206 records from Aves Marinas y Playeras en el PNN Sanquianga y la Bocana de Iscuandé entre 2007 y 2009. 5 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 6 records from Inventario de Aves en la Finca Naranjitos; Aracal, Yopal, Casanare. 11 records from Aves de Caño Cristales, La Macarena, Meta. 2 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 3 records from Umgebung der Gesamtschule Hamburg-Winterhude. 92 records from Mountain Invasion Research Network (MIREN) survey. 2 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 11 records from BUND - Dassower See (Lübeck/Dassow). 363 records from Données naturalistes de Monsieur François FOURNIER. 3 records from Birds and plant species near Petushki town (Vladimir region). 970 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 64 records from Herbario de la Universidad de Sevilla. 2 records from NHMO DNA Bank Other groups collection. 24 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1086 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 17 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 2 records from Leben im Finkensteiner Moor. 185 records from Pittsburg State University, Theodore M. Sperry Herbarium. 838 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 1968 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 5 records from Peces asociados a raíces de manglar en el PN Morrocoy, Venezuela. 5 records from Mamíferos colectados en la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 1 records from Birdrace-Herford-Birder-Herford. 2 records from Expedición Providencia I - INVEMAR. 26 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 222 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Trawl. 18 records from Schulzentrum "Parc Hosingen". 1 records from Die Wuhle. 1 records from Lindesnes. 7 records from Cuxhavener Küstenheiden. 1 records from vegoek. 2758 records from University of Michigan Museum of Zoology, Division of Birds. 1 records from Signalement d'espèces exotiques envahissantes - Export mai 2018 de la base de données du GEIR. 34627 records from Hatikka.fi observations. 55 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 4 records from Données naturalistes de Monsieur JOURDE Rémi. 1 records from Grundschüler erkunden Schulumgebung. 28 records from Données naturalistes de AUNEAU Florent. 116 records from Données du parc national de la Vanoise. 2 records from Ice Algae Barents Sea. 2773 records from inatura - Erlebnis Naturschau Dornbirn. 70 records from Galiano Island BC Canada Marine Zoology 1893–2021. 23 records from UEL - Coleção de Peixes - Museu de Zoologia da Universidade Estadual de Londrina. 9 records from Aves de la Ecoreserva CPF Cupiagua (Aguazul, Casanare) - Proyecto FIBRAS. 206 records from Images and observations of mostly edible plants in Stephen Barstow’s Edible Garden in Norway, taken between 2005 and 2014. 6 records from Banco de Germoplasma Vegetal del Jardín Botánico de Olarizu (Vitoria-Gasteiz)/Olarizuko Lorategi Botanikoaren Landare Germoplasma Bankua (Vitoria-Gasteiz). 128 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 11230 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 3 records from Ictiofauna del sistema lagunar costero Chacahua-La Pastoría, Oaxaca. 96 records from Inventaire de la flore de Lot-et-Garonne 2013. 1 records from Données du/de la naturaliste Verna Eric provenant de la base de donnée du SINP Île-de-France CETTIA. 32 records from Herbario de Universidad de Murcia: MUB. 1 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 410 records from NSW AVH data. 2 records from BIRDRACE Oostfreesland Bird-Lopers. 3 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 32336 records from Birds ringed with Norwegian rings 1961-1990. 1611 records from Local floras of Russia: a compilative dataset. 2 records from Caracterización del ANP Parque Nacional Arrecifes de Xcalak y formulación de un programa de monitoreo. 23 records from Collection of Cyclostomata and Fish from Nizhyn Gogol State University. 317 records from SPC PROCFish/C Fish Observations Fiji 2002-2003. 277 records from Norfish: Shetland Cod Fishery 1520-1796. 3 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 10 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 1 records from Données espèces - Expertise IPE 69. 426 records from Riqueza específica, distribución y abundancia de aves acuáticas en la ensenada de La Paz, Baja California Sur, México. 2 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 38 records from Clare Biological Records Centre Dataset 2004-2007. 64 records from IOW Natural History & Archaeological Society Marine Invertebrate Records 1853- 2011. 2 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 7 records from Caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 11 records from Diatom assamblage in samples from sediment trap OG5. 19 records from 2019_nsmk_biodiversity_observations_bi_10237. 4 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 6375 records from National Trust for Scotland Species Records. 406 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 7 records from Inventaire Oiseaux. 7 records from Seed bank grassland. 10 records from 2020_biodiversity_information_specimen_cnu. 61 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 3 records from Wanderweg am Windebyer Noor (bei Eckernförde). 1 records from Flora vascular de Torca, Localidad de Usaquén (Bogotá - Colombia). 502 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 3 records from Flora und Fauna im Brexbachtal. 19 records from Senckenberg - CeDAMar Resource. 6 records from MICROBIS database. 15878 records from Estonian Ornithological Society (BirdLife Estonia). 2 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 2 records from Birdrace-Professorenteam-Münster. 164 records from Ontario Breeding Bird Atlas 1981-1985. 89 records from RSPB Reserves breeding bird surveys. 1 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1 records from Inventaire de la flore de la Vienne 2011. 2147 records from Vascular Plant Herbarium, UiB. 97 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 83 records from Fish (KIWE-PI). 30 records from Benthos counted on dredged samples during Valdivia cruise VA53. 4 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 9 records from Carabidae of the European North-East of Russia. 1 records from BIRDRACE federleser. 158 records from Some botanical researches of the Faculty of Biology of Taras Shevchenko national university of Kyiv (1930s-2000s). 30 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1 records from Données naturalistes de Severine GUYOT. 10 records from A checklist of seed plant of Gaoligongshan National Nature Reserve. 1 records from BIRDRACE Die Borner. 12 records from Briòfits d'Andorra. 36 records from Insect Specimens of Kitami Region Museum of Science History and Art. 3 records from Fish species occurrences in the Tana River Basin, Kenya, digitized from the Ichthyology collection at the National Museums of Kenya and from recent field expeditions. 239 records from CAS Botany (BOT). 18509 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 335 records from Specimen based records and geographic locations of carabid beetles (Coleoptera) collected mainly by Dr. Kazuo Tanaka. 22 records from Données naturalistes d'Anaïs MAS. 4 records from BIRDRACE Upupa epöpse. 4 records from UB - Herbário da Universidade de Brasília. 4 records from Greenland macrobenthos 2006. 178 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV (Ejemplaresimagenes). 2 records from North Atlantic and Arctic Cumacea sampled during the IceAGE (2011) and PASCAL (2017) project. 13392 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 19 records from Inventaire biodiversité du site Pierre Fabre de Puylaurens. 3921 records from Wikiplantbase #Toscana. 4 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 25 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 8057 records from BioFokus. 180 records from Anymals+plants - Citizen Science Data. 69 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 143 records from DASSH Data Archive Centre volunteer sightings records. 1 records from Tartu University fossil collections. 10 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 43520 records from Aranzadi Ringing Scheme (bird ring-recovery data). 955 records from Vogeltrekstation (NL) - Historical Data on Timing of Ringing of Nestling Birds. 1 records from Rechts des Inn Höhe Hofau Rosenheim. 774 records from ABV - Common breeding birds in Flanders, Belgium (post 2016). 392 records from TTU Mammals Collection. 16 records from Biological data from the Soviet Antarctic Expedition (1955-1958). 17 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1 records from Aves marinas de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 30 records from Data on the biodiversity of macrophyte communities and associated aquatic organisms in lakes of the Vologda Region (North-Western Russia): macrophytes. 2 records from Inventaire biodiversité du site Pierre Fabre de Bagnères de Bigorre. 11 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 563 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from BIRDRACE Di-Bi-Di-Birder. 22 records from DBG Tissue and DNA Bank. 285 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 7 records from Biodiversidad asociada al proyecto Parque Solar Fotovoltaico Tepuy. 4 records from "Tre Pini" (Montebelluna, Italien). 1 records from BIRDRACE Professorenteam. 1 records from Données du/de la naturaliste Champagne Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Birdrace-Easy_Birders-Plön. 5 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 3 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 3248 records from EDP Foz-Tua: Vascular Flora and Habitats – Ecological and Complementary Measures Monitoring Programs – Construction Phase II [2015-2016] and Flooding Phase [2016-2017]. 29675 records from Bumblebees and butterflies in Norway. 77 records from KUZ Herbarium: collections of vascular plants. 5 records from Mollusca of Costa Rica (INBio). 3 records from Rosa gallica L. in "Medobory" Nature Reserve. 1 records from Im Bauerngarten. 125 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 3 records from Biodiversidad de los Ecosistemas Mesofóticos de la Isla de San Andrés. 1 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 224 records from NRA River corridor survey data from 1990s - River Colne and Tributaries. 8 records from Flora vascular acuática de la cuenca del Río Tamesí. 801 records from Shire Group IDB species data 2004 to present. 531 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 3 records from Línea base general derivada de sonidos unidireccionales (espectro audible) para el valle medio del Magdalena - VMM. 1 records from Mamíferos Asociados al Cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 45 records from Données de la structure Seine-et-Marne Environnement provenant de la base de donnée du SINP Île-de-France CETTIA. 2309 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 340 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 3 records from WildesMoor bei Schwabstedt. 2 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 38 records from The Erysiphales Collection at the Botanische Staatssammlung München. 199 records from Données du Parc Naturel Régional de la Haute Vallée de Chevreuse provenant de la base de donnée du SINP Île-de-France CETTIA. 265 records from ZooplanktonBeaufortSeaNOGAP2. 6 records from FBIP: Offshore Benthic Macrofauna Data. 3 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 14 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 1 records from Plantas del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 161 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE258. 109 records from Central Siberian Botanical Garden Herbarium (NS, NSK). 6610 records from Soviet Trawl Fishery Data (New Zealand Waters) 1964-1987. 1 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 34 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 6 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 27 records from Birds (NMNO-BI). 2 records from NCSM Mammalogy Collection. 8 records from Biodiversidad del microfitoplancton marino en la zona económica exclusiva limítrofe del Pacífico central mexicano. 3 records from HCF herbarium - Universidade Tecnológica Federal do Paraná - Campus Campo Mourão - Herbário Virtual REFLORA. 275 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 1 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 3 records from Nivå Bay species list, Zealand, Denmark. 22 records from Chondrichthyans Of Ireland. 12 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 1 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 102 records from Norfolk and Suffolk Broads Invertebrate Data 2007-2008. 45 records from Données naturalistes de Matthias COLIN. 4 records from Colección general del plantas vasculares del Herbario JBB. 2265 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 1 records from Seabird sightings in Ghana and Ivorycoast. 4 records from Avifauna asociada al área boscosa del resguardo indígena Cuti, municipio de Unguía, Chocó. 2020. 6 records from Chronicle of Nature - Phenology of Plants of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 1 records from Albury Wodonga Nature Map. 35 records from Jardín Botánico Atlántico, Gijón/Xixón: Herbarium JBAG. 86 records from CSIRO, Abundance and distribution of orange roughy in southeast Australian waters 1987-1979. 3 records from Weinberg Reichersdorf. 73 records from Natural history museum data on Canadian Arctic marine benthos. 20 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 3 records from Plant Systematics Laboratory, Ajou University, Korea. 106 records from Waterbird counts, Luomus dataset. 1679 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Vascular Plant Herbarium. 82 records from II Atlas of nesting birds - target species (1999-2005). 24 records from FBIP: SeaKeys - iziko_cartilaginous_fish. 4 records from BIRDRACE Raumpatrouille Oriolus. 4 records from Fish Fauna of Berlin. 5 records from Woodmeadow Invertebrate Survey 2014. 15 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 1286 records from CONN. 3781 records from NHMO Bird collection. 1 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 4 records from Kherson State University herbarium (KHER), Department of Botany. 3 records from Post Graduate College Bannu Herbarium. 1 records from Macrozoobenthos composition, abundance and biomass in the Arctic Ocean along a transect between Svalbard and the Makarov Basin 1991. 76 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from MfN - Fossil plants (Mesophytic). 15424 records from Estonian Naturalists’ Society. 34134 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 1 records from Floristic and avifauna finds in the vicinity of the village of Mala Berezyanka. 2 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 3 records from Wildlife Observations Bardon Hill 31.5.09. 1 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 1 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano (Larvas de peces). 4 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 596 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 12 records from Plantas Vasculares de Chile – Herbario VALPL - Universidad de Playa Ancha. 2 records from Seaweeds records from Argentina and Uruguay. 90 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 719 records from Base de données faune - DREAL Centre-Val de Loire. Polygones. 39 records from Collection botanique Le Grand A. (BOUM). 4 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 304 records from WADFW PSAMP W1993. 48 records from HBRG Other Invertebrates Dataset. 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 1290 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 399 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 3 records from Royal Belgian Institute of Natural Sciences Echinodermata collection. 4630 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 8 records from IPOE_Schnack_Polychaeta. 12920 records from Kastikka Literature Sources. 1187 records from Marsh Monitoring Program - Amphibians. 63 records from SEWBReC Algae and allied species (South East Wales). 16 records from Larval fish at time series station Helgoland Roads, North Sea, in 2004. 674 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 7 records from CSIRO, Cruise SS199101, Marine Biology Data, Western Australia, 1991. 348155 records from iNaturalist Research-grade Observations. 7 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 3 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 653 records from Total phytoplankton inventory in the western part (Grote Rede, Negenvaam, Buiten Ratel, Oost Dyck) of the North Sea between 1977 and 1978. 349 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 538 records from Fife non-breeding bird 5km atlas 1991-99. 177 records from Diversidade e ocorrência de peixes em Inhambane (2009-2017). 2 records from Plant species occurrences recorded from selected sites in the upper Tana River Basin, Kenya. 26 records from Appalachian State University, I. W. Carpenter, Jr. Herbarium. 2550 records from Conchological Society of Great Britain & Ireland: marine mollusc records. 9 records from SPC CoFish Fish Observations Niue 2005. 603 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2018. 2 records from Hintere Halde. 90 records from Visual sightings from Song of the Whale 1993-2013. 1 records from Mittelriede Höhe Gliesmarode-Braunschweig. 1 records from Outer Hebrides Insect Records from Literature. 31 records from Spermatophyta specimens of Iwate Prefectural Museum. 233 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from Stadt Königs Wusterhausen. 23 records from Atlas of Life in the Coastal Wilderness. 2444 records from Naturalis Biodiversity Center (NL) - Coleoptera. 18 records from Marine algal flora of Flores and Corvo Islands, Azores. 2 records from Tiergarten (Zeitz). 127 records from Vascular Plant Specimens of Kochi Prefectural Makino Botanical Garden. 2 records from Ökologischer Weinberg (Guntersblum). 1 records from Molluscus specimens of Toyohashi Museum of Natural History. 332 records from Wikiplantbase #Sardegna. 2 records from Aves de la expedición en Monte y Pinal, Boyacá - Proyecto Boyacá BIO. 12 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 253 records from Grassland Survey of Central Region, 1989-90. 1 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 1 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 42 records from Polish seed gene bank – historical passport data of accessions. 30 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 3 records from Wedeler Au. 6 records from Mißmahlsche Anlage. 2 records from flower availability 2008 Schorfheide. 379 records from SEWBReC Beetles (South East Wales). 2 records from Ruhrwiesen bei Neheim-Hüsten. 18 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz (CCDE-IEOCD). 9 records from Elasmobranquios mexicanos. 470 records from Intermountain Herbarium (Vascular plants & algae). 31 records from Trawl-survey data in the Adriatic Sea (Mediterranean) collected in 1972, 1975 and 1981. 1 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 15 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 12 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua (Mamíferos). 102 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 6 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 2 records from ncf-birds-nigeria. 99 records from River Blackwater historic river corridor surveys. 13 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 3 records from Küstenschutzwald. 2 records from BIRDRACE Griffin Wood Warblers. 3 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 3 records from Données espèces -expertise IQE 3. 1 records from MBML-Mamiferos - Coleção de Mamíferos. 228 records from Flora of the Volga River basin. 4 records from NEON Biorepository Aquatic Plant, Bryophyte, Lichen and Macroalgae Collection (Herbarium Vouchers [Standard Sampling]). 161 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 1 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 557 records from Auckland Museum Botany Collection. 7 records from Project for Reef Fish Monitoring. 21 records from Mamíferos de 14 municipios del Departamento del Valle del Cauca para el fortalecimiento de RNSC y Caracterización de Predios Adquiridos para la Conservación de Cuencas. 6 records from FBIP:IZIKO-UCT:Historical Survey (1930-1980). 1347 records from PRECIS. 632 records from Derek Lott Coleoptera Dataset. 104 records from Inventaire de la flore des ENS des Pyrénées-Atlantiques 2011-2012. 2 records from WADFW PSAMP W1996. 111 records from Moss occurrences in the Kuznetsk upland (Altai-Sayan mountain country). 1 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 21 records from Biological Collection, National Institute of Oceanography, Goa, India. 23 records from Atlas de la Biodiversité de Seine-et-Marne - volet 2. 186 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 9 records from Monitoreo de la Fauna Silvestre con Capacitación y Certificación de Monitores Comunitarios en las Microrregiones Prioritarias para la Conectividad y Conservación de la Biodiversidad Agua Blanca, Cañón del Usumacinta, Sierra de Tabasco, *. 2 records from Unser Schulgelände. 1 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 14 records from South Caribbean Diversity. 13 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 6 records from Primer monitoreo y seguimiento de fauna terrestre para el AID y AII de la Pequeña Central Hidráulica Riofrío. 2018. 76 records from InboVeg - Amphibious vegetation of shallow lakes at Turnhout. 2 records from Birdrace-Alte_Socken-Cuxhaven. 62 records from Moss occurrences of the Great Vasyugan Bog system. 3 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 103 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 10 records from Pollen analysis of sediment profile WO1 from Wollingster See. 117 records from Derbyshire Invasive Non-Native Species (INNS) 1900 - 2014. 6 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 150 records from Botany registration database by Danish botanists. 923 records from Carnet B Centre - lot 2012. 21 records from UNCW Right Whale Aerial Surveys 2008. 72 records from Invasive species - Invasive plants near waterways in West and East Flanders, Belgium. 143 records from Heteroptera collections of SW Finland. 22 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE262. 3 records from Données de la structure Pie verte bio provenant de la base de donnée du SINP Île-de-France CETTIA. 45 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 20 records from Collection Ichthyologie - SNSD. 13 records from National Museum Of Marine Science & Technology. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 207 records from NYSM Birds. 35 records from Avifauna de los Parques Ecológicos Distritales de Montaña del Distrito Capital. 25 records from Biodiversity mapping in connection with Nature in Norway (NIN) in Troms and Finnmark, Norway (2018). 1 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 2 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 4 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 9 records from Données espèces Expertise IQE 311. 9 records from MMS Surveys, SCB 1995-1997. 17 records from SPC CoFish Invertebrates Observations Cook Islands 2007. 20 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidráulica de Calima. 2018. 18 records from India Biodiversity Portal publication grade dataset. 12 records from Phytoplankton abundance during ARGOS cruise Argos90/8. 48 records from Données du naturaliste Pierre Rivallin provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Birdrace_Die_Borner-Viersen. 131 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 11 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 265 records from Inventaire de la flore de Charente-Maritime 2015. 25 records from UWBM Invertebrate Paleontology Collection. 25 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 4927 records from Oiseaux de France métropolitaine en hiver 1977-1981. 12 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 2 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 6 records from Données du naturaliste Thibedore Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Colección de Artropodos del Museo de Historia Natural Marina de Colombia - Makuriwa. 135 records from Bosque Mesófilo de Montaña de México. 3755 records from Annual Census on Waterfowl (Anatidae) Population. 4 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 1 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 1 records from Fortalecimiento del herbario SERO. 3 records from Study of epibenthos and demersal fish in and around the dredging areas of the Belgian Continental Shelf (1977-1981). 6 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, February - December 2019. 843 records from DMNS Bird Collection (Arctos). 3 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 2237 records from Parc_National_de_Port_Cros_2017_12_18. 1 records from Birdrace-WdW-Wilder_Westen-Viersen. 308 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from MAG Herbarium: collections of vascular plants. 8 records from Collection ornithologique A. Maës. 390 records from MPM Milwaukee Public Museum Herbarium. 201 records from Zooplankton Species Distribution and Abundance Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise, August 2017. 84 records from mabik_di. 23 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 5016 records from observe_tuna_bycatch_ecoscope. 948 records from Inventaire de la flore de Dordogne 2018. 136 records from 2018_nsmk_biodiversity_pi. 1 records from Marine macroalgae species from Dominican Republic. 4 records from Pflanzen und Tiere im Burgwald. 60 records from Herbario de la Universitat de les Illes Balears. 6 records from Zooplankton community and pelagic copepods in Tudor creek (Mombasa, Kenya) between 1984 and 1987. 1 records from Örtzemündung (Stedden). 2 records from 人禾環境倫理發展基金會_2017-2019東北部獨流溪魚蝦蟹螺調查. 96 records from Hexacorallians of the world. 1147 records from Naturalis Biodiversity Center (NL) - Aves. 13 records from Inventaire biodiversité du site Pierre Fabre du Carla à Burlats. 3254 records from Eremaea. 1033 records from Marine Offshore Seabed Survey data held by JNCC. 766 records from KUBI Ornithology Collection. 1 records from Données naturalistes de Françoise SERRE-COLLET. 30 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 73 records from Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. 12 records from Distribution of surface phytoplankton between New Zealand and Antarctica, December 1957. 57 records from Herbarium of Taiwan Forestry Research Institute. 41 records from UKSBA Cyprus - Habitat Samples, 2019. 1 records from Schulgarten Zinnowwald-Grundschule. 8 records from Inventario de Aves Mámbita. 2 records from Fishing with motorized boats in the Belgian littoral area in 1932. 4 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves de los Complejos de Páramos de Sonsón y Urrao. 1028 records from UK Cranefly Recording Scheme - records verified via iRecord. 6 records from Biologische Station im Kreis Wesel. 2 records from Schiller Gymnasium Hof 10b. 13 records from Specimen-based records of geometrid, pyralid, and crambid moths (Lepidoptera) with location information from the collection of Dr. Hiroshi Inoue. 732 records from Données naturalistes de Damien AVRIL. 1 records from USWTR Onslow Bay Aerial Survey -Right side- 2008-2010. 2 records from Australian Institute of Marine Science (AIMS) - CReefs Ningaloo Reef Biodiversity Expedition, Australia (2008 - 2010). 438 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 23 records from Santa Barbara Museum of Natural History Entomology Collection. 2 records from BIRDRACE Gätkes Erben. 102 records from 1915-2016 Department for Environment Food & Rural Affairs (Defra), Marine Strategy Framework Directive (MSFD) Collation of invasive non-indigenous species. 2 records from Naturalis Biodiversity Center (NL) - Echinodermata. 42 records from JCT AVH data. 236 records from University of Tennessee Bryophyte Herbarium. 6 records from Nature-type mapping in Norway (Viken) 2020. 11 records from Colecção Botânica do Instituto de Investigação Agrária de Moçambique. 148 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 6 records from Données espèces - Expertise IQE 41. 1 records from Streuobstwiese Kattenhund (Schleswig). 222 records from Censo de ardeidas invernantes y nidificantes de la Comunidad Autónoma del País Vasco. 36 records from Larval fish at time series station Helgoland Roads, North Sea, in 2005. 10 records from Likona Invertebrates. 27 records from Inventaire de la flore de Charente 2013. 9 records from Caracterización de la fauna y flora presente en los predios propuestos para el plan de restauración del distrito de conservación de suelos del cañon de rio grande (DCS-CRG), en el municipio de Dagua. 3275 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 1 records from VFD-H: MIttelgebirgsweide. 4 records from Weidenhüttendorf an der Würm (München). 277 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 1 records from Liste d'espèces animales recensées au cours des activités de l'Organisation pour le Développement Durable et la Biodiversité (ODDB ONG) au Bénin. 18 records from Tidlig oppdagelse og varsling av fremmede arter 2018. 3 records from Inventaire et suivi Faune. 275 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 21 records from University of California Museum of Paleontology. 46 records from DBRC Hemiptera species records 1969 to 2015. 316 records from Observatoire Pelagis aerial surveys 2002-2021. 1 records from BB-Biodiversität a. 303 records from Dreal Corse - Base Ogreva. 11 records from Plantas exóticas en ecosistemas de montaña de Chile – LIB-MIREN Non-native plants in mountain ecosystems of Chile – LIB-MIREN. 875 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 36 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2017. 1 records from Birdrace-Halsbandschnäpper-Stuttgart. 96 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 108 records from University of Tennessee Vascular Herbarium. 133 records from Bryophyte Herbarium, Oslo (O) UiO. 4986 records from NEFSC Right Whale Aerial Survey. 510 records from SD - SD Herbarium, San Diego Natural History Museum. 2 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 199 records from Diversidade e ocorrência de peixes na Zambézia (2003-2016). 1 records from MCCC - Mendocino College Coast Center Herbarium. 12 records from Phytoplankton abundance in surface water in January 1996, Callao, Peru. 1 records from BIRDRACE Bielefinken. 2 records from BIRDRACE Guckers Offenbach. 1036 records from UWBM Ornithology Collection. 95 records from Cumbria Non Native Invasive Species. 649 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 102164 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 4 records from Données espèces - Expertise IQE 31. 2 records from Données espèces - Expertise IPE 6. 420 records from Vegetation of the Rybachy Peninsula and the Sredny Peninsula, Murmansk Oblast, Russia. 1 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 5 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 5 records from SNH Invertebrate Site Condition Monitoring 2015: Mount Bog SSSI. 4 records from Données espèces - Expertise IPE 15. 52 records from Biodiversidad asociada al gasoducto Loop San Mateo-Mamonal. 138 records from Dénombrement des oiseaux d'eau du Sénégal de 2016 à 2018. 3 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México (Coleoptera). 4 records from Diatom assamblage in samples from sediment trap OG4. 38 records from Moss occurrences in Kuznetsk depression (Altai-Sayan mountain country). 1 records from Données du naturaliste Arnaud Horellou. 1 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 2773 records from England Non Native Species records 1965 to 2017. 89 records from Non Native Species Across Wales (1989 to 2012). 56 records from Abundance of benthic infauna in surface sediments from the North Sea sampled with TYRO in 1986. 15 records from PonTaurus collection. 19 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 896 records from CNS AVH data. 6 records from INSDC Host Organism Sequences. 46 records from Auckland Museum NZ Marine Collection. 49 records from Phytoplankton sampling in the coastal waters of south eastern Tasmania, Australia (2009-2015). 3 records from Gronau - auf der Suche nach dem Neunauge. 1 records from Coastal Marine Environment Targeted loci environmental. 3 records from Abundance of phytoplankton in the Marmara Sea collected during the Bilim 2 cruise in Oktober 2008. 36 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 114 records from Eden Arthropod Azores Database. 75 records from Inventaire de la flore des Pyrénées-Atlantiques 2007-2008 - Littoral. 1 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 6 records from Artsrike vegkanter i Haugesund. 6 records from Natura 2000 Etang de Lachaussée et zones voisines. 9 records from SPC PROCFish/C Invertebrates Observations New Caledonia 2003 to 2008. 1268 records from AUM Fish Collection. 1 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 1 records from Entdeckertour am Muldestausee 1/05. 713 records from University of Colorado Museum of Natural History Herbarium Vascular Plant Collection. 32 records from Abundance and distribution of coastal, inshore zooplankton in the Huon Estuary and D'Entrecasteaux Channel, Tasmania, Australia (2004-2005). 153 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Peces San cristóbal). 3 records from Flora del municipio de Culiacán, Sinaloa. 3 records from Woodmeadow Botanical Survey 2018. 51 records from CSIRO, Fish Survey, Albatross Bay - Gulf of Capentaria, North Australia, 1986-1988. 1 records from Fish community in Gazi Creek sampled between November 1990 and April 1991. 49 records from 2019_NSMK_IN. 3 records from BIOTOPE_2017_12_18. 1 records from Répertoire des espèces de poisson inventoriées dans le fleuve Niger, de Niamey à Say. 263 records from Demersais survey in the Azores between 1996 and 2013. 8 records from Plants of Ukrainian flora from collections of M. I. Berezhnyj. 7 records from Ghent University - Zoology Museum - Vertebrate collection. 699 records from ARKO kulturmarkseng. 1 records from BIRDRACE Diesmal sehen wir mehr. 6 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 18 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 2 records from Données du/de la naturaliste Allayaud Manon provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 126 records from Casual records for Scottish Wildlife Trust reserves - Verified data. 3 records from Données espèces - Expertise IQE 44. 123 records from Inventaire de la flore du PNRLG 2016 (Gironde). 123 records from Jeu de données convention Eurovia-SPN-2012-2016. 4 records from Artenvielfalt Kreis Gießen. 2 records from Birdrace_Gätkes_Schergen-Helgoland. 1 records from Birdrace-Enger_am_Spektiv-Herford. 5578 records from Florida Keys Reef Visual Census 2000. 2 records from IOV Fitoplancton del Saco del Golfo de Cariaco, Venezuela. 36 records from BLM CETAP SHIP Sightings. 28 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 621040 records from Ringing and recovery database of birds (TIPU). 1 records from Western Australian Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 1 records from Ecosystem biomonitoring with eDNA: metabarcoding across the tree of life in a tropical marine environment. 1 records from Observations individuelles - Parc naturel régional de Lorraine. 2 records from Umgebung der Grundschule Oderberg. 51 records from Données d'observateurs divers (observateurs transmettant un nombre de données peu élevé) saisies dans Cettia-idf. 1 records from Galathea II, Danish Deep Sea Expedition 1950-52. 1 records from Inventaire des papillons nocturnes sur le territoire de la métropole Rouen Normandie. 13 records from Phenological Center - Birds (Karelia). 3 records from Aves de la cuenca media del río Chambery, Caldas. 952 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - non-sensitive species. 1 records from Hochschule Zittau/Görlitz. 2 records from Steinbruch Mainz-Weisenau. 581 records from SBC LTER Darwin Core Archive: Kelp Forest Reef Fish Abundance. 29 records from Fauna y flora del municipio de Lipa, Arauca. 10 records from BioGIS - Fish - INPA database. 2 records from pflanzendiversitaet_2008_sch_alb_hai_aktualisiert. 1 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 71 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 42 records from Fish: Records for Kent.. 302 records from Phytocenoteca of the laboratory of ecosystem theory (Plants). 1 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 6 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 808 records from Distribution of 15 major fish species in the North Sea between 1959 and 1979. 109 records from Sperm morphology of 264 songbird species. 1 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 1926 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 28 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 7 records from Plants of the Botanical Garden of Surgut State University (Surgut, Russia). 3 records from Birdrace-Nord_Seh_Team-Nordfriesland. 16 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 1 records from Données naturalistes de Pierre-Alexis RAULT. 535 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 219 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 1 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 2 records from Fuchsloch (Mohlsdorf/Ostthüringen). 3 records from Données du naturaliste Esnault Sarah provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Données du naturaliste Sébastien Siblet. 3 records from Taxonomic diversity of true bugs (Hemiptera: Heteroptera) in open biotopes along power lines. 39 records from Underwater video and still-image dataset of fishes and other aquatic animals in Lake Biwa, Japan, observed via carp-mounted video loggers.. 3 records from Streuobstwiese Stedar. 2 records from Caracterización Ecológica de la Ornitofauna del Humedal Costero Obregón. 2 records from Plymouth sound dataset. Soft sediment macrobenthos from the Plymouth Sound from 1995. 149 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 10 records from Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 14 records from Quantitative and Semi-quantitative survey of the vegetation of Seychelles through stand scale plots. 7 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2006. 193 records from Entomology Division, Yale Peabody Museum. 230 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 6 records from Données de la structure Département 78 provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Pollen profile from Achenhang. 223 records from Lizard Island Research Station. 3 records from Literature review of the Scheldt estuary with emphasis on the biotic components. 17184 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 2 records from Artenvielfalt der Nordsee - Sylt. 15 records from étude entomologique et plan de gestion de la forêt de bréviande. 481 records from Steiermärkisches Landesmuseum Joanneum - Herbarium GJO. 35 records from Vascular Plants Collection of Sagamihara City Museum. 1 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 11 records from Phytoplankton abundance in surface water in February 1998, Pisco, Peru. 15 records from Natura 2000 Forêt de la Reine. 111 records from Vascular Plants, Observations, Oslo (O). 69 records from The AAU Herbarium Database. 121 records from Inner Oslofjorden Phytoplankton Database. 128 records from Vascular Plant Herbarium at the Kandalaksha Strict Nature Reserve (KAND), Russia. 1 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 1 records from New and remarkable leafhoppers and planthoppers (Hemiptera: Auchenorrhyncha) from Switzerland. 231 records from North East Scotland Mosses and Liverworts (1950-2014). 1 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 4 records from Museu Paraense Emílio Goeldi - Mollusca Collection. 384 records from BioGIS - Vascular plants - A. Danin's grid database. 10 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 2 records from Données naturalistes de ZIBERLIN Olivier. 22458 records from Biodiversitätsdatenbank Salzburg. 7 records from Heritage Trees of Ireland. 8 records from flower visitor interactions 2008. 197 records from ZooplanktonBeaufortSeaNOGAP1. 564 records from IMOS Plankton Collection - AusCPR: Zooplankton Abundance. 58 records from Données espèces - Expertise IQE 92. 212 records from OBI - Robert F. Hoover Herbarium, Cal Poly State University. 11 records from Aquatic vascular plants of the Middle Urals (Sverdlovsk region, Russian Federation). 1 records from Collection Polychaeta - ZSRO. 217 records from imr_mareano_rpsledge. 1 records from Plant specimens of Mie Prefectural Museum. 5 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 270 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 11 records from DREAL_PACA_2017_12_18. 84 records from Fauna y flora asociada a la Central Hidroeléctrica Playas. 12 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 38 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 2 records from Binsenwiesen. 1 records from Colección de Mamíferos del Museo de Historia Natural C.J. Marinkelle. 6 records from FURB herbarium - Universidade Regional de Blumenau - Herbário Virtual REFLORA. 32 records from Zooplankton Bering Strait Tiglax 1991. 6 records from Inventaire de la flore de la Vienne 2016. 1544 records from Leicestershire and Rutland Environmental Records Centre records pre 2000. 3465 records from Miscellaneous records held by BIS. 90 records from Données sur la biodiversité des récifs coralliens de Martinique (OMMM). 10 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 4192 records from Leicestershire and Rutland Environmental Records Centre records 2010-2014. 642 records from NMNH Material Samples (USNM). 2 records from Données naturalistes de Laurent PONCET. 1 records from Données naturalistes de WITTS Antony. 31 records from Colección Mastozoológica de la Universidad Distrital Francisco José de Caldas. 86 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 19 records from Study of epibenthos and demersal fish of the titanium dioxide discharge area in the Dutch Continental Shelf (1976-1981). 2 records from NABU-Auerochsenweide. 1 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba. 16 records from UWBM Mammalogy Collection (Arctos). 225 records from Données faune de Luc BARBARO. 345 records from Données faune Indre Nature 2016-2017. 4 records from Colección de los peces nativos de Sonora. 14 records from Mamíferos del piedemonte de la sabana de la Orinoquia. 110 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 137 records from Echinoids_occurrences_Southern_Ocean. 87 records from Livre rouge de la flore menacée de France (tomes I et II) - (FCBN). 25 records from Butterfly_conservation_2017_12_18. 66 records from Inventaires faune. 325 records from University of British Columbia Herbarium (UBC) - Algae Collection. 15 records from Chronicle of Nature - Phenology of Birds of Sikhote-Alin State Nature Biosphere Reserve Named After K. G. Abramov. 1 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 23 records from Aves de México I. 4139 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 12 records from BCE butterfly data central and southern Europe. 826 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 12 records from Inventaire biodiversité du site Pierre Fabre de Lavaur Les Cauquillous. 1 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 6 records from Fremmede arter - Planteimport, Engebråten Planteskole. 341 records from imr_mareano_grab. 2 records from Conservación de la agrobiodiversidad de la Milpa Tarahumara, Chihuahua. 1 records from Düne am Ulvenberg (Darmstadt). 114 records from Protected species bycatch in New Zealand fisheries. 780 records from Snow Entomological Museum Collection. 112 records from ISU Birds. 2 records from City of Edinburgh Natural Heritage Service - Fungi Surveys. 57 records from Mammals housed at MHNG, Geneva. 61 records from ALA species sightings and OzAtlas. 1 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (2), 2011 - Données faune. 35 records from 2017_nsmk_observations_pi. 186 records from Löydös Open Invasive Species Observations. 7 records from Observasjoner av plantearter ved kartlegging av naturtyper etter Miljødirektoratets instruks 2018-2021. 1 records from Grillhütte Wettsaasen, Wiese, Hecken. 64 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 182 records from Cowan Tetrapod Collection - Birds. 132 records from Temporal evolution of zooplankton, surface observations, in the Northwestern Mediterranean Sea, Villefranche-sur-mer 1898-1917. 4 records from Canto de los andes Chingaza- patrones de actividad vocal diaria y anual en aves de montaña. 1139 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 11537 records from Florida Keys Reef Visual Census 2009. 499 records from Italian official Adriatic (Mediterranean Sea) landings between 1953 and 2012. 3 records from Overvåking av dragehode Dracocephalum ruyschiana. 32 records from RNF - Données de l'association de la RN du lac de Remoray. 8413 records from Long term data from the Hanko Bird Observatory (Halias data). 3 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 47 records from Gwaii Haanas Marine Plants (OBIS Canada). 77074 records from Waarnemingen.be - Bird occurrences in Flanders and the Brussels Capital Region, Belgium. 6 records from Inventaire des Invertébrés marins de la Réserve Naturelle Nationale de Saint-Martin. 17 records from DASSH Data Archive Centre expert sightings records. 5 records from Distribución y abundancia de aves marinas y acuáticas en regiones marinas prioritarias y áreas protegidas del Golfo de California y Golfo de México. 1448 records from BIOGEOnet : Bryophytes occurrences in Wallonia. 2 records from Vascular Plant Herbarium: Herbarium Generale. 2 records from 2019_nsmk_biodiversity_ms_1000. 5 records from Monitoreo biológico en la cuenca Jamundí - Subcuenca Pance Campaña ARA - RARE - CVC – Asociación Calidris. 1 records from artsprosjektet_52-14_cirripedia. 30 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 928 records from NOAA Pacific Islands Fisheries Science Center, Ecosystem Science Division Coral Reef Ecosystem Program, Rapid Ecological Assessments of Fish Belt Transect Surveys (BLT) at Coral Reef Sites across the Pacific Ocean from 2000 to 2009. 238 records from Bottom Trawl Surveys: Catch and Effort Data For South East Australia, 1898-1996. 4 records from données bibliographiques diverses (non araignées). 19 records from Plants of Ghana. 22 records from University of Cincinnati, Margaret H. Fulford Herbarium - Bryophytes. 228 records from RNF - Association Loiret Nature Environnement. 36 records from AMAPPS Northeast Aerial Cruise Fall 2012. 188 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 94 records from Taiwan New Year Bird Count. 128 records from UAM Herpetology Collection (Arctos). 44 records from Epibenthos and demersal fish monitoring in function of aggregate extraction in the Belgian part of the North Sea. 105 records from Michigan State University Herbarium Vascular Plants. 3 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 15 records from Bryophytes from a study of primary producer traits across an altitudinal gradient in alpine Finse. 171 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 15 records from Total phytoplankton inventory in the Southern Bight of the North Sea in 1971. 17 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 37648 records from FLORIVON. 97 records from Naturalis Biodiversity Center (NL) - Mollusca. 13 records from Étude de lépidoptérologie comparée. 1 records from coastal suspended particulate matter North Sea surface Raw sequence reads. 1031 records from Flora of the Stołowe Mts.. 96 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Olekminsky. 361 records from Crustacea collection (TSZCr) UiT Tromsø Museum. 1 records from Données de la structure Département 95 provenant de la base de donnée du SINP Île-de-France CETTIA. 108 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 12 records from Caracterización biológica en la Serranía de San Lucas 2015. 324 records from N3 data of Kiel bay. 6 records from Bird specimens of Komatsu City Museum. 5703 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2017.. 117 records from Biodiversidad acuática del río Amacuzac, Morelos, México (Peces). 79 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 1 records from BIRDRACE VdW Wilder Westen. 173 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. 1 records from Données espèces - Expertise IPE 123. 8 records from FBIP:ELM: Malacology Collections. 533 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 2 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 1 records from Inventaire et dénombrement des oiseaux du Parc Naturel Communautaire de la Vallée du Sitatunga (Sud Bénin). 13 records from Bryophyte specimens of Toyama Science Museum. 89 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 14 records from Borders Backyard Biodiversity. 8 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 1 records from BIRDRACE Die Göttinger Sozialbrachvögel. 7 records from Macroalgas del área de influencia del terminal marino de la empresa Salinera Sacosal, Araya, Estado Sucre, Venezuela. 225 records from Royal BC Museum - Invertebrates Collection. 8 records from AMAPPS Northeast Aerial Cruise Spring 2012. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 5 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 6 records from Inventaire des Algues de Polynésie française. 1 records from Birdrace-LiLaMai-Vechta. 65 records from Data-set of Moth Specimen from TESRI. 6 records from WADFW PSAMP W2004. 18 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidroeléctrica de Calima. 2017-B.. 6059 records from Bird Atlas 2007 - 2011. 14 records from City of Edinburgh Natural Heritage Service - Ranger Ad-hoc records and sightings. 1913 records from Manscape. 32 records from Aves en fincas ganaderas sostenibles del Meta. 3 records from Camera trapping bird data. 11 records from Arizona State University Mammalogy Collection. 21 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 925 records from Inventaire de la flore des Landes 2015. 6 records from Marine algal (seaweed) flora of Terceira Island, Azores. 15 records from Biodiversidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 2 records from Plantas de la expedición en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 216 records from Kastikka Small Collections. 25 records from Herpetofauna, avifauna y plantas de Puerto Salgar, Caparrapí, Guaduas y Quebradanegra (Cundinamarca). 1 records from Collection Crustacea - SNSD. 65 records from Mayfly (Ephemeroptera) Data for Great Britain for 1906-2017. 29 records from Composition and distribution of the biomass of zooplankton in the central Arctic Basin 1975, 1976, 1977. 86 records from Occurrence data from various smaller projects in Norway. 20 records from Marine Fishes from Archipielago los Roques, Venezuela. 5 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 1139 records from Sheffield Bird Study Group (Yorkshire records). 17 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea, in 2008. 2 records from Gaïadomo_2017_12_18. 40 records from PAMP-tracheo: Vascular plants in Ribera Occidental de Navarra (Spain). PhD project, L. Garde. 261 records from Digitalización y Sistematización de las Colecciones Biológicas Nacionales del Instituto de Biología, UNAM (Plantas vasculares). 4 records from BTCV wildlife counts recording workshops. 4 records from Hydrate Ridge, OR - Deep sea cold seep ecosystem Targeted Locus (Loci). 3 records from Colección del Herbario de la Universidad Católica de Oriente. 2 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 271 records from Norfish: Spanish and Basque Newfoundland Cod Fishery 1520-1790. 161 records from SPC CoFish Fish Observations Palau 2007. 33 records from William F. Barr Entomological Museum. 7 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 3 records from Biodiversidad asociada al Estudio de Impacto Ambiental del campo de producción Cumanday. 16 records from Scientific Results of the New Zealand Government Trawling Expedition, 1907. 1 records from Schafheide im Böblinger Wald. 7 records from Données naturalistes de Pierre NOEL (M2MNHN2010). 1259 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 3 records from CU Invertebrate Paleontology. 4 records from Chronicle of Nature - Phenology of Plants of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 1 records from Bell Museum algae. 1 records from La Planète Revisitée, massif du Mitaraka, mission principale (février-mars 2015). 1418 records from Carpatica Operation. 1 records from GEO-Tag am Hohlen Stein. 2 records from Données naturalistes de CASTEL Thierry. 9 records from Monitoreo biológico en la cuenca RUT, campaña ARA - RARE - CVC – Asociación Calidris. 197 records from Instituto de Botánica Darwinion. 2 records from Vegetation relevés of pine forests (Moscow region). 283 records from RNF - Données du Conservatoire d'espaces naturel Limousin. 1 records from Données espèces - Expertise IPE 53. 1 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 134 records from AMNH Mammal Collections. 11 records from Phytoplankton abundance in surface water in November 1997, Chimbote, Peru. 4161 records from Manx Biological Recording Partnership VERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 1 records from AIRELE_2017_12_18. 27 records from PAMP-tracheo: Vascular plants in Pamplona and surroundings (Navarra, Spain). Undergraduate thesis, R. Mayo. 494 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 8 records from Peces de arrecifes coralinos de Isla Larga y Alcatraz, PN San Esteban, Venezuela. 2407 records from ABV - Common breeding birds in Flanders, Belgium. 4 records from Vascular plants in Danish coastal meadows. 41 records from Brigham Young University Life Science Museum (BYU) Mammal Collection (Arctos). 270 records from Bernice P. Bishop Museum. 177 records from Arizona State University Ichthyology Collection. 16 records from BioGIS - Fish - HUJ collections. 1 records from Classic localities of fishes from the Western Balkans. 2149 records from Natural England Marine Monitoring surveys. 3356 records from 2019_nsmk_fish. 1 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: deuxième partie.. 403 records from Ground Beetle Recording Scheme - data verified via iRecord. 3 records from IOV - Distribución espacial y temporal del fitoplancton en el Golfo de Cariaco. 1 records from Collection Tunicata SMF. 90 records from Danish waterbugs (Insecta: Hemiptera-Heteroptera: Gerromorpha + Nepomorpha). 21 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 1 records from Insect (GNHM-IN). 1071 records from Karplanter i vernet barskog og edelløvskog. 210 records from Marine Species Records from Skomer Marine Conservation Zone (MCZ) Marine Monitoring Programme. 67 records from Inventarios de fauna y flora en los DRMIs Embalse Peñol - Guatapé y Cuenca Alta del Río Guatapé, Las Camelias y el área a declarar Cuenca de San Pedro. 2 records from Collection botanique É. Juttin (BOUM). 3 records from Herbario de Plantas Vasculares del Museo Municipal de Ciencias Naturales 'Lorenzo Scaglia' MMPEAAH. 1 records from Données naturalistes de Martin HILAIRE. 1 records from Données espèces - Expertise IQE 20. 3 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Poliquetos Chetumal). 1 records from Stadtbiotop Ulrichteich. 4 records from Collection contest. 8 records from Inventaire de la flore des Deux-Sèvres 2014. 72 records from Insect specimens of Hokkaido University. 362 records from Fife breeding bird tetrad atlas 1991-99. 40 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 21 records from The Lepidopterists' Society Season Summary. 1 records from Waldwandel in Monschau-Mützenich-Boverei. 110 records from Zooplankton studies in the Southern Bight of the North Sea between 1971 and 1974. 851 records from MSB Bird Collection (Arctos). 44 records from Naturhistorisches Museum Mainz, Zoological Collection. 30 records from Données de la structure CERF (Centre d'Etude de Rambouillet et de sa Forêt) provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Zukünftiges NSG Höftland/Bockholmwik. 149 records from Finds of Lepidoptera species in the steppe zone of Ukraine according to some literature resources. 45 records from Données naturalistes de Loïc SALAUN. 1 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 2064 records from Ichthyology Collection - Royal Ontario Museum. 8 records from Línea base del medio biótico en los bosques para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguablanca -El Morro Yopal. 18 records from Fig. 4. Simplified macrofossil concentration in sediment core Lz1116. 44 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 72 records from Caracterización ecológica y de la diversidad en los ecosistemas de arrecifes de coral y pastos marinos en la jurisdicción marina de CORPAMAG, departamento del Magdalena, Caribe Colombiano. 3 records from Comunidad íctica de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 152873 records from Other BSBI Scottish data up to 2015. 45 records from Total phytoplankton inventory in the Scheldt estuary on the 19th of March 1974. 4 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 66 records from Pteridophyte of the Urals and adjacent areas. 6 records from Données naturalistes acquises sur les sites du MNHN. 1 records from Institut Mediterrani d'Estudis Avançats (CSIC-UIB): IMEDEA-INSECTA. 14 records from Données naturalistes de Wilfried RATEL. 1 records from mabik_al. 12 records from NEFSC 1999 aj9902. 5 records from Glasgow Museums BRC: Hemiptera. 80 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 33 records from RNF - Données du Syndicat de Gestion des Gorges de l'Ardêche. 73 records from Inventaire des Poissons de la région du Diahot (RAP). 1 records from Evaluation of the effect of disposal of dredging material on macrobenthos communities in the Maas plain (1988). 20 records from Actualización e incremento de la base de datos del Herbario de la Benemérita Universidad Autónoma de Puebla. 9 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 1 records from BIRDRACE Grenzgänger. 251 records from Données naturalistes de Julien BIRARD. 3 records from Données espèces - Expertise IQE 52. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 2 records from BIRDRACE Wannacks Topti(c)ker. 11 records from Caracterización de Fauna para el plan de Etnodesarrollo de Bahía Cupica, Chocó. 20 records from PIROP Northwest Atlantic 1965-1992. 718 records from UWFC Ichthyology Collection. 48 records from Macroalgas marinas de la Región de Zihuatanejo, Gro.. 5 records from Données du Naturaliste Louis Albesa. 1 records from Auburn University Museum of Natural History Invertebrates. 1 records from BIRDRACE Unterste Niederrhein-Rennvögel. 2 records from Steinbachtal (Würzburg). 2 records from Wirbach. 6387 records from Pacific Multispecies Small Mesh Bottom Trawl Survey. 3 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 7 records from Vascular plant specimens of The Shirakami Research Center for Environmental Sciences, Hirosaki University. 25920 records from Atlas of Finnish Macrolepidoptera. 6 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 2 records from BIRDRACE leucorhö statt logorrhö. 31 records from Faune-Réunion - export oiseaux 31/12/2017. 6 records from Fern (Pteridophyta) specimens of Toyama Science Museum. 24 records from EDP Foz-Tua: Vascular Flora – Complementary Studies and Baseline Year of the Ecological Monitoring Program [2011]. 1826 records from Mohonk Preserve Vernal Pool Amphibian Breeding Ecology Monitoring from 1931 to Present. 1 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Eggs/Nests (Arctos). 14 records from University of British Columbia Botanical Garden Collections (UBCBG). 2132 records from Merseyside BioBank (unverified). 98 records from Intertidal Biodiversity along the Portuguese coast (2001-2002). 2 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 1 records from Beetles (Coleoptera) of the state natural monument “Pine forests on the shifting sands” in the Oka River valley (Peremyshlsky district of Kaluga region, Russia). 1595 records from CUMV Fish Collection. 3 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 305 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from MUST, Insecta. 52 records from GRENHA_2017_12_18. 9238 records from Données ONF faune-flore-fonge. 1 records from Observations occasionnelles dans la RNN Etang de Saint-Paul avant le 31/12/2017. 4454 records from The New York Botanical Garden Herbarium (NY). 29 records from Richard Staniforth Herbarium (UWPG). 1 records from BIRDRACE Stuttgart 100 trööt. 4 records from Regroupement de données rhopalocères récoltées sur la période de 2010-2015 par Cistude Nature. 1 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 2 records from Colección Ictiológica del Museo de La Salle Bogotá (MLS). 5 records from Inventario de Aves en la Finca la Reserva, Yopal, Casanare. 766 records from Institut Botanic de Barcelona (IBB, CSIC-Ajuntament de Barcelona), BC-Plantae. 15 records from The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 1390 records from Herpetology Collection - Royal Ontario Museum. 1 records from University of Michigan Museum of Zoology, Division of Mollusks. 10 records from Data from CRSN herbarium digitization initiative under BID-funded project. 35 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE206. 144 records from Opportunistic records of marine megafauna in Suriname. 13 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 10 records from Agnes Marion Ayre Herbarium (NFLD). 36 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest. 4781 records from Florida Keys Reef Visual Census 2003. 4 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 79 records from IMOS National Reference Stations (NRS) Phytoplankton Abundance and Biovolume. 706 records from Herbarium of Jyväskylä University Museum. 354 records from Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 51 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE278. 2 records from Données opportunistes. 551 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 1 records from Grünes Germersheim. 475 records from DASSH Data Archive Centre Academic Surveys. 56 records from Données de la structure Département 77 provenant de la base de donnée du SINP Île-de-France CETTIA. 221 records from POPA- Fisheries Observer Program of the Azores: Fish caught to be used as bait in the Azores tuna fishery from 1998 to 2013. 22 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 14 records from Freshwater Diversity Identification for Europe (FREDIE) - funded by the German Leibniz association ( SAW-2011-ZFMK-3). 321 records from Akita Prefectural Museum, Insect Collection. 1 records from BIRDRACE Die Lippegeier. 2 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 8 records from Fauvel P. 1937. The fishery grounds near Alexandria. XI.Annelida Polychaeta. Notes et memoires No 19. 5031 records from Dry Tortugas Reef Visual Census 2006. 37801 records from ECNASAP - East Coast North America Strategic Assessment. 5 records from Expedición ornitológica en el municipio de Barbacoas (Nariño) - BIO Alas, cantos y colores. 78 records from Données naturalistes de Philippe GOURDAIN. 3 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 296 records from DAV - UC Davis Herbarium. 1 records from Nationalpark Jasmund. 1 records from Exkursion Ebertsheimer/Grünstädter Berg. 477 records from University of Florida Invertebrate Paleontology. 1 records from BIRDRACE Die Kartoffelsäcke. 6 records from Fishes in MZNA-VERT: distribution of freshwater blenny in the Segre and Susia rivers (Spain). 6 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 2 records from Collection Polychaeta SMF. 72 records from MCNH Museum of Cultural and Natural History Fish Collection. 4 records from Schule Sulzbach (Oberegg). 62 records from Inventaire des Ephémères de métropole (Opie). 81 records from Tetrápodos de Uruguay. 19 records from National Register of Monumental Trees. 1 records from BIRDRACE Falkenberger Fluppis. 1949 records from Chronicle of Nature - Phenology of Plants of Caucasian State Biosphere Reserve of the Ministry of Natural Resources. 125 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 3 records from Artenvielfalt im Rhein-Neckar-Raum. 53 records from The Ecology of the Inshore Marine Zooplankton of the Chukchi Sea near Point Barrow, Alaska. 303 records from Lepidoptera World (Luomus) (LEPW). 576 records from University of New Hampshire - Macroalgal Collection. 151 records from mabik_iv. 27 records from Phytoplankton of coastal waters in Aegean Sea, Eastern Mediterranean, 2002-2003.. 31 records from Herbarium of Namur. 251 records from UAM Bird Collection (Arctos). 4 records from Données espèces - Expertise IQE 2. 8041 records from Dry Tortugas Reef Visual Census 2014. 45984 records from Observations floristiques - plateforme SINP régionale SILENE PACA. 1 records from Schulhof und Anlagensee in Nellingen. 10 records from Monitoreo Ambiental del Proyecto La Colosa. 1 records from Birdrace-Berlin_Sparrows-Uckermark. 19 records from UTEP Herpetology Osteology (Arctos). 3 records from Données espèces - Expertise IPE 96. 2 records from BIRDRACE OAG Neuwerk. 144 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 4 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 1 records from marine metagenome Raw sequence reads. 41 records from SPC CoFish Fish Observations Nauru 2005. 1 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 41 records from Insecta collection of Museum of Natural and Environmental History, Shizuoka. 1 records from Kindervilla Aussengelände/ Hiltroper Park. 11 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México. 25843 records from SA Fauna (BDBSA). 95 records from Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 501 records from Prairie Fen Biodiversity Project. 50 records from Finds of species of animals, fungi and plants from particular territories of Podesinnia. 2 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 2 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 1 records from Stadtpark Schmölln. 11 records from Sistematización de la Colección de Algas Marinas del Centro Interdisciplinario de Ciencias Marinas CICIMAR-IPN. 3721 records from Welsh Invertebrate Database (WID). 1 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 14 records from Données naturalistes de LEVEQUE Antoine. 1 records from ZUEC-BRY - Coleção de Bryozoa do Museu de Zoologia da UNICAMP. 56 records from Miscellaneous Vascular Plants. 444 records from BV Insectarium Virtual. 220 records from AMAPPS Northeast Aerial Cruise Spring 2017. 33 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 12361 records from Freshwater fish of the Netherlands, 1800-2019. 48 records from Kitami Region Museum of Science History and Art(KIRM). 2 records from Données du/de la naturaliste MANN Gérard provenant de la base de donnée du SINP Île-de-France CETTIA. 626 records from IMOS National Reference Station (NRS) - Zooplankton Abundance. 1380 records from Long-Term Monitoring Network Vegetation Quadrats. 1 records from Caracterización de la ornitofauna del Alto del Buey, Bahía Solano, Chocó. 8 records from Fuldaaue (Stadtgebiet Fulda). 2409 records from Bell Museum plants. 1 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 2 records from fauna_do_municipio_de_araraquara-sp. 80 records from Données naturalistes de Pierre FRAPA. 2 records from Collection Crustacea ZMG. 1 records from Naturpark Kottenforst-Ville 16.6.09. 299 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 43 records from Vascular plant specimens of Akita Prefectural Museum. 5856 records from Inventaire permanent de la flore du massif armoricain. 1 records from Plant Observation Records of Japan. 62 records from All observations extracted from the Flora of Northumberland and Durham 1831. 12 records from Biodiversidad acuática del río Amacuzac, Morelos, México (Plantas Acuaticas Río Amacuzac). 4 records from BIRDRACE Dithmarscher Deichhühner. 474 records from Monitoreo participativo de aves en la laguna de Fúquene. 5 records from WADFW PSAMP S1993. 41 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 35 records from Proyecto COL88611 para la conservación y uso sostenible de ecosistemas secos. 29 records from Vertebrats d'Andorra. 16 records from Phytoplankton abundance in surface water in October 1997, Ilo Peru. 16 records from Caracterización de la avifauna asociada al cerro Alto Santa Fe, Guarato, 2019. 94 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 467 records from CSIRO Ichthyology provider for OZCAM. 49 records from Australian Institute of Marine Science (AIMS) – Zooplankton community composition of Darwin Harbour, Northern Territory. Australia (2002 - 2004). 11 records from Données naturalistes de BILLI Frédéric. 6 records from Fish (MNHM-PI). 38 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herbario SCLC). 147 records from Threatened species occurrences, Denmark 1991-2015. 2 records from Bayerische Donau - Neu Ulm. 34 records from NATURALIA_2017_12_18. 2 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 31 records from Inventaires PnrL "Etangs". 28 records from Marine algal flora of Santa Maria Island, Azores. 376 records from Herbarium Senckenbergianum (FR). 6 records from Données naturalistes de Dominique GALLAIS. 18 records from MSB Host Collection (Arctos). 363 records from Invertebrate Zoology Division, Yale Peabody Museum. 646 records from Merseyside BioBank Active Naturalists (unverified). 67 records from UCM Bird Collection (Arctos). 3713 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Gill Net. 483 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Bay Trawl. 2 records from Mamíferos de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 1 records from BIRDRACE Die Wetterauer. 324 records from CHSC - CSU Chico, Chico State Herbarium - Vascular Plants. 5 records from La Colección de Poliquetos (Annelida: Polychaeta) de la Facultad de Ciencias Biológicas, Universidad Autónoma de Nuevo León. 76 records from UCT: South Africa Seaweeds(1905-2008). 1 records from Données naturalistes de Frédéric CHICHE. 899 records from Danish True Bugs. 118 records from Yorkshire Naturalists Union Marine and Coastal Section Records. 189 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, A. C., Centro Regional del Bajío. 59 records from Species within North Ayrshire from 1984 - Present. 3 records from Parc naturel régional de Lorraine "Chantiers Natures". 5 records from IPS Golfs. 103 records from Herbario de la Facultad de Farmacia de la Universidad Complutense de Madrid (MAF). 1 records from Données du naturaliste Luc Berger. 1522 records from Israel Nature and Parks Authority. 3 records from Mozambique_Fish_Collections. 2 records from Pottundkopp. 5 records from Monitoreo de peces arrecifales y tiburones parte de los valores objetos de conservación (VOC) en el santuario Malpelo para el año 2020. 246 records from fundiv france database. 1 records from Données naturalistes de Guilène PROCIDA. 4 records from Catálogo de insectos de la colección del Centro de Entomología. 111 records from Colección de Mamíferos (Mammalia) del Museo de Historia Natural de la Universidad de Caldas, Colombia. 62 records from Données naturalistes de Pierre NOEL (stage). 69 records from Macrobenthos monitoring at long-term monitoring stations in the Belgian part of the North Sea between 1979 and 1999. 3 records from Herbarium of Yugra State University. 2 records from Landschaftsschutzgebiet Schmutterwald. 39 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 779 records from Données naturalistes de Thomas GAILLARD. 1 records from Human observations belonging to Biorehab Klepsland. 6 records from Moluscos Arrecifes Coralinos San Esteban Carabobo Venezuela. 3 records from Tag der Artenvielfalt. 4 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 16 records from Algal community on the pneumatophores of mangrove trees of Gazi Bay in July and August 1987. 56 records from Heuschrecken_Raw1. 22 records from MPM Herpetology. 116 records from Données Faune de l'Agence des Espaces Verts (AEV) d'Ile de France. 14 records from Frost Entomological Museum. 8 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 13 records from The Wildlife Information Centre - BioBlitz Events. 18 records from Aves del Distrito de Páramos en los departamentos de Nariño-Putumayo. 103 records from Fairchild Tropical Botanic Garden (FTG). 7 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 3211 records from Northern Ireland Environment Agency (NIEA) Collated Species Records. 1 records from Woodmeadow Invertebrate Survey 2017. 25 records from COMARGIS: Information System on Continental Margin Ecosystems. 11 records from Finds of rare insects and plants in the Black Forest, Kirovohrads'ka Oblast', Ukraine. 7239 records from National Trust Species Records. 10 records from Aves asociadas a tres ventanas de la Orinoquia Colombiana - SULU I. 189 records from Australian National Wildlife Collection provider for OZCAM. 10 records from Fish Collections at the South China Sea Repository and Reference Centre, Universiti Malaysia Terengganu, Malaysia. 3 records from HUSC - Herbário Unisanta. 152 records from Consultancy Contract Surveys - Marine Species Records. 41 records from Marine algal (seaweed) flora of Graciosa Island, Azores. 1 records from Données naturalistes d'Emmanuel ICARDO. 164 records from CUMV Amphibian and Reptile Collection. 1 records from Birdrace-do_elster_Dortmund. 54 records from Système d’évaluation de l’état des Eaux (SEEE) - Invertébrés. 32 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE275. 267 records from NHM, Heteroptera. 4 records from City of Edinburgh Natural Heritage Service - Bonaly Bird Survey. 2 records from Algae, Norwegian College of Fishery Science. 9895 records from Miscellaneous records held on the Cofnod database. 4 records from Données espèces - Expertise IQE 86. 46 records from Abundance and biomass of zooplankton collected in front of the Danube Delta in May and September 1979. 1 records from Langes Tannen(LMS), Klasse 5d. 170 records from CSIRO, fish surveys by the Courageous, 1978-1979. 10 records from Biodiversidad de Mamíferos de las Reservas Naturales de la Sociedad Civil del Parque Natural Regional Páramo del Duende, Valle del Cauca, Colombia. 24 records from Pollen profile from site Kolbermoor2, Rosenheim, Oberbayern, Germany. 143 records from Colección de Artrópodos de la Asociación BIGA para el estudio del patrimonio natural de Galicia: ABIGA. 71 records from Données naturalistes de David HAPPE. 2 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 162 records from Inventaires du Conservatoire botanique national méditerranéen dans le cadre de l'ATBI Mercantour.. 4240 records from NSW BioNet Atlas. 174 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 45 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 26 records from Entomological Collection (GNM). 1 records from Données de la structure CORIF/LPO-idf provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Données espèces - Expertise IQE 85. 2 records from Estudio de la comunidad zooplanctónica y fitoplanctónica en los ecosistemas de arrecifes coralinos mesofóticos del Parque Nacional Corales de Profundidad. 1 records from CSIRO, Cruise SS200803, Marine Biological Survey, Great Australian Bight; South Australian and Tasmanian continental slope, 2008. 2 records from HeathNet data. 178 records from Inventaire permanent des invertébrés de Haute-Normandie. 8 records from GEO Biodiversity Day. 7 records from DREAL_PACA_-_N2000_-_Commune_de_Névache_2017_12_18. 4 records from Reappraisal of Synagrops Günther, 1887 with rehabilitation and revision of Parascombrops Alcock, 1889 including description of seven new species and two new genera (Perciformes: Acropomatidae). 1 record
Keywords: GBIF; biodiversity; species occurrences